Optical laminate

CN122945196APending Publication Date: 2026-10-20SUMITOMO CHEM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202610454254.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-11
Filing Date
2026-04-08
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0023]根据本发明,提供能够兼顾更严酷的高温高湿环境下的耐裂纹性的提高和隔着太阳镜的不均的减少的光学层叠体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention provides an optical laminate that can simultaneously improve crack resistance in harsher high-temperature and high-humidity environments and reduce unevenness when viewed through sunglasses. The optical laminate sequentially comprises a first protective layer, a linear polarizer, a first adhesive layer, a second protective layer, and a phase retardation layer. The first adhesive layer is a cured layer of a curable composition containing a cationic polymeric compound. The phase retardation layer, starting from the first adhesive layer side, sequentially comprises a first liquid crystal phase retardation layer, a second adhesive layer, and a second liquid crystal phase retardation layer. The thickness of the second adhesive layer is less than 100 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to optical laminates. Background Technology

[0002] Optical stacks of linear polarizers and multiple liquid crystal phase retardation layers have long been known as anti-reflective circular polarizers for reflective image display elements such as OLEDs. It is also known that, from the viewpoint of protecting the linear polarizer, protective layers are used to hold both sides of the linear polarizer in such optical stacks (see, for example, Patent Document 1).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-052365 Summary of the Invention

[0006] The problem that the invention aims to solve

[0007] However, in applications using optical laminates, there is room for improvement in balancing enhanced crack resistance in harsher high-temperature and high-humidity environments with reduced unevenness through sunglasses.

[0008] The present invention was made in view of the above-mentioned problems, and its object is to provide an optical laminate that can simultaneously improve crack resistance in harsher high temperature and high humidity environments and reduce unevenness through sunglasses.

[0009] Methods for solving problems

[0010] [1] An optical laminate comprising, in sequence, a first protective layer, a linear polarizer, a first adhesive layer, a second protective layer, and a phase difference layer.

[0011] The first adhesive layer described above is a cured layer of a curable composition containing a cationic polymeric compound.

[0012] The aforementioned phase retardation layer stack comprises, sequentially from the first adhesive layer side, a first liquid crystal phase retardation layer, a second adhesive layer, and a second liquid crystal phase retardation layer.

[0013] The thickness of the second adhesive layer is less than 100 nm.

[0014] [2] According to the optical laminate described in [1], when all cationic polymeric compounds are set to 100 parts by mass, the curable composition of the first adhesive layer contains 20 to 80 parts by mass of an alicyclic epoxy compound.

[0015] [3] According to the optical laminate described in [1] or [2], wherein the cationic polymeric compound of the curable composition of the first adhesive layer contains an oxetane compound.

[0016] [4] An optical laminate according to any one of [1] to [3], wherein the second adhesive layer is a water-based adhesive layer.

[0017] [5] According to the optical laminate described in [4], the thickness of the second adhesive layer is 20 nm or less.

[0018] [6] An optical laminate according to any one of [1] to [5], wherein the second protective layer is a triacetyl cellulose resin film.

[0019] [7] According to any one of [1] to [6], the optical stacked body, when the in-plane phase difference value of the above phase difference stacked body for light with wavelength λnm is set as Re(λ), satisfies the following relationship (1) and (2).

[0020] 80nm≤Re(450)≤130nm (1)

[0021] Re(450) / Re(550)≤1.00 (2)

[0022] Invention Effects

[0023] According to the present invention, an optical laminate is provided that can simultaneously improve crack resistance in harsher high temperature and high humidity environments and reduce unevenness through sunglasses. Attached Figure Description

[0024] Figure 1 This is a schematic cross-sectional view of one embodiment of an optical laminate 400.

[0025] Explanation of reference numerals in the attached figures

[0026] 30… First liquid crystal phase retardation layer, 40… Second adhesive layer, 50… Second liquid crystal phase retardation layer, 150… First adhesive layer, 180… First protective layer, 220… Linear polarizer, 300… Phase retardation layer stack, 400… Optical stack (circular polarizer). Detailed Implementation

[0027] (Optical laminate (circular polarizer) 400)

[0028] like Figure 1As shown, the optical laminate 400 of the embodiment sequentially includes a first protective layer 180, a linear polarizer 220, a first adhesive layer 150, a second protective layer 190, and a phase difference layer laminate 300, and can function as a circular polarizer.

[0029] (Linear polarizer 220)

[0030] Linear polarizers have the function of selectively transmitting linearly polarized light in a certain direction from unpolarized light such as natural light. Examples of linear polarizers include films formed by uniaxially stretching a dichroic pigment such as iodine or organic dichroic dyes in a polymer such as PVA (hereinafter also referred to as "polarizers"), and optically anisotropic layers formed by orienting dichroic pigments and polymeric liquid crystal compounds (hereinafter also referred to as "polarizing films").

[0031] The polarization performance of a linear polarizer can be measured using a spectrophotometer. For example, in the visible light range (380 nm to 780 nm), a spectrophotometer equipped with a prism polarizer can be used to measure the transmittance (T1) along the transmission axis (orientation perpendicular direction) and the transmittance (T2) along the absorption axis (orientation direction) using the two-beam method. Regarding the polarization performance in the visible light range, the individual transmittance and degree of polarization at each wavelength are calculated using the following equations (Equation 1) and (Equation 2). Visibility correction is then performed using the 2-degree field of view (C-light source) of the JIS Z8701, thereby allowing the calculation of the individual transmittance (Ty) and the degree of polarization (Py) corrected for visibility. Furthermore, based on the similarly measured transmittance, the L value is calculated using the color matching function of the C-light source. * a * b * (CIE) Colorimetric a in the color system * and b * This allows us to obtain the hue of a single linear polarizer (single-unit hue), the hue of linear polarizers arranged in parallel (parallel hue), and the hue of linear polarizers arranged orthogonally (orthogonal hue). * and b * The closer the value is to 0, the more neutral the hue can be.

[0032] Monomer transmittance (%) = (T1 + T2) / 2 ··· (Equation 1)

[0033] Degree of polarization (%) = (T1 - T2) / (T1 + T2) × 100 ··· (Equation 2)

[0034] The visibility-corrected polarization degree Py of a linear polarizer is typically 80% or higher, preferably 90% or higher, more preferably 95% or higher, even more preferably 98% or higher, particularly preferably 99% or higher, and can be 99.9% or higher. Increasing the visibility-corrected polarization degree Py of a linear polarizer is advantageous in improving the anti-reflective function of optical laminates. If the visibility-corrected polarization degree Py is less than 80%, it may sometimes fail to perform its anti-reflective function when used as an anti-reflective coating.

[0035] A higher transmittance Ty of the visibility-correcting monomer in a linear polarizer increases the clarity of white displays. However, as shown in Equations (1) and (2), excessively increasing the transmittance leads to a decrease in polarization degree. Therefore, a transmittance of 30% or more and 60% or less is preferred, more preferably 35% or more and 55% or less, further preferably 38% or more and 50% or less, even more preferably 40% or more and 45% or less, and most preferably 41% or more and 43% or less. If the transmittance Ty of the visibility-correcting monomer is too high, the polarization degree Py becomes too low, sometimes resulting in insufficient anti-reflective function when used as an anti-reflective film.

[0036] <Polarizer>

[0037] A membrane that has been uniaxially stretched while impregnating a polymer such as a polyvinyl alcohol (PVA) resin membrane with iodine or an organic dichroic dye can typically be manufactured through the following steps: a step of uniaxially stretching the polyvinyl alcohol resin membrane; a step of dyeing the polyvinyl alcohol resin membrane with a dichroic dye such as iodine to adsorb the dichroic dye; a step of treating the polyvinyl alcohol resin membrane with the adsorbed dichroic dye with a crosslinking agent such as a boric acid aqueous solution; and a step of washing with water after treatment with a crosslinking agent such as a boric acid aqueous solution.

[0038] The thickness of the polarizer is typically 30 μm or less, preferably 18 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. This thickness is typically 1 μm or more, for example, 5 μm or more.

[0039] Uniaxial stretching of polyvinyl alcohol (PVA)-based resin films can be performed before, simultaneously with, or after dyeing with dichroic pigments. When uniaxial stretching is performed after dyeing, it can be done before or during boric acid treatment. Of course, uniaxial stretching can also be performed in multiple stages as shown here. Uniaxial stretching can be performed by: stretching uniaxially along the film transport direction between rollers with different circumferential speeds; stretching uniaxially along the film transport direction using heated rollers; stretching along the width direction using a tenter frame, etc. Furthermore, uniaxial stretching can be performed by dry stretching in the atmosphere or by wet stretching while the PVA-based resin film is swollen using a solvent such as water. The stretching ratio is typically around 3 to 8 times. Alternatively, an aqueous solution containing PVA can be coated onto a thermoplastic resin film, dried, and then stretched together with the thermoplastic resin film using the methods described above.

[0040] The dyeing of polyvinyl alcohol (PVA) resin films using dichroic pigments can be carried out, for example, by immersing the PVA resin film in an aqueous solution containing a dichroic pigment. Specifically, iodine or dichroic organic dyes can be used as dichroic pigments. It should be noted that the PVA resin film is preferably pre-treated by immersion in water to induce swelling before dyeing.

[0041] When using iodine as a dichroic dye, the dyeing method typically involves impregnating a polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide. The iodine content in this aqueous solution is typically approximately 0.01 to 1 part by weight relative to 100 parts by weight of water, and the potassium iodide content is typically approximately 0.5 to 20 parts by weight relative to 100 parts by weight of water. The temperature of the aqueous solution used for dyeing is typically around 20 to 40°C. Furthermore, the impregnation time (dyeing time) in this aqueous solution is typically around 20 to 1,800 seconds.

[0042] On the other hand, when using dichroic organic dyes as dichroic pigments, a common dyeing method involves impregnating a polyvinyl alcohol-based resin film in an aqueous solution containing the water-soluble dichroic organic dye. The content of the dichroic organic dye in this aqueous solution is typically about 0.0001 to 10 parts by weight relative to 100 parts by weight of water, preferably 0.001 to 1 part by weight. This dye aqueous solution may contain inorganic salts such as sodium sulfate as dyeing auxiliaries. The temperature of the dichroic organic dye aqueous solution used in dyeing is typically about 20 to 80°C. Furthermore, the impregnation time (dyeing time) in this aqueous solution is typically about 10 to 1,800 seconds.

[0043] Boric acid treatment following dyeing with a dichroic pigment can be performed by immersing the dyed polyvinyl alcohol-based resin film in an aqueous solution containing boric acid. The boric acid content in the aqueous solution is typically about 2 to 15 parts by weight relative to 100 parts by weight of water, preferably 5 to 12 parts by weight. When iodine is used as the dichroic pigment, the aqueous solution containing boric acid preferably contains potassium iodide. The potassium iodide content in the aqueous solution is typically about 0.1 to 15 parts by weight relative to 100 parts by weight of water, preferably 5 to 12 parts by weight. The immersion time in the aqueous solution containing boric acid is typically about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the aqueous solution containing boric acid is typically above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.

[0044] Boric acid-treated polyvinyl alcohol (PVA) resin membranes are typically subjected to a water washing process. This washing can be performed, for example, by immersing the boric acid-treated PVA resin membrane in water. The water temperature during the washing process is typically around 5–40°C. Furthermore, the immersion time is typically around 1–120 seconds.

[0045] After washing, a drying process is performed to obtain a polarizing film. The drying process can be carried out using a hot air dryer or a far-infrared heater. The drying temperature is typically around 30–100°C, preferably 50–80°C. The drying time is typically around 60–600 seconds, preferably 120–600 seconds. Through the drying process, the moisture content in the polarizing film is reduced to a practical level. Its moisture content relative to the total mass of the polarizing film is typically around 5–20% by mass, preferably 8–15% by mass. If the moisture content is above 5% by mass, the polarizing film has sufficient flexibility, thus preventing damage or breakage after drying. Furthermore, if the moisture content is below 20% by mass, the polarizing film has sufficient thermal stability.

[0046] As described above, it is possible to manufacture polarizers formed by adsorbing dichroic pigments onto a polyvinyl alcohol-based resin film.

[0047] <Polarizing film>

[0048] From the perspectives of being able to arbitrarily control the hue, being able to achieve significant thinning, and having non-shrinkage properties due to the absence of thermal stretching relaxation, polarizing films, which are optically anisotropic layers of polymers containing dichroic pigments and polymeric liquid crystal compounds, can be suitable for applications such as flexible displays.

[0049] A polarizing film is formed by coating a polarizing film forming composition onto an alignment film formed on a substrate as needed, and orienting the dichroic pigments contained in the polarizing film forming composition. The polarizing film has a thickness of 0.1 μm or more and 5 μm or less, more preferably 0.3 μm or more and 4 μm or less, and even more preferably 0.5 μm or more and 3 μm or less. If the film thickness is thinner than this range, the desired light absorption may not be obtained, and if the film thickness is thicker than this range, there is a tendency for orientation defects to easily occur due to the reduced orientation constraint force of the alignment film. Furthermore, the polarizing film forming composition may further include solvents, photopolymerization initiators, photosensitizers, polymerization inhibitors, leveling agents, and adhesion enhancers.

[0050] For an optically anisotropic layer in which the dichroic pigment and polymeric liquid crystal compound are horizontally aligned with respect to the substrate surface, the ratio (dichroic ratio) of the absorbance A1(λ) in the orientation direction for light with wavelength λnm to the absorbance A2(λ) in the direction perpendicular to the orientation plane is preferably 7 or more, more preferably 20 or more, and even more preferably 40 or more. The higher this value, the better the absorption selectivity of the polarizer. Although it also depends on the type of dichroic pigment, in the case of a liquid crystal cured film cured in the state of a nematic liquid crystal phase, it is about 5 to 10.

[0051] By mixing two or more dichroic pigments with different absorption wavelengths, polarizing films of various hues can be produced, including polarizing films that absorb across the entire visible light spectrum. By creating polarizing films with such absorption properties, they can be applied to a wide range of applications.

[0052] <Polarizing films; polymeric liquid crystal compounds>

[0053] Polymerizable liquid crystal compounds refer to compounds that possess polymerizable groups and liquid crystal properties (hereinafter also referred to as polymerizable liquid crystals). Polymerizable groups are groups that participate in polymerization reactions, preferably photopolymerizable groups. Here, photopolymerizable groups refer to groups that can participate in polymerization reactions through active free radicals, acids, etc., generated by a photopolymerization initiator described later. Examples of polymerizable groups include: vinyl, ethoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, ethylene oxide, oxetyl, etc. Among these, acryloyloxy, methacryloyloxy, ethoxy, and oxetyl are preferred, and methacryloyloxy or acryloyloxy are more preferred. The liquid crystal property can be thermotropic liquid crystal or lyotropic liquid crystal; when mixed with dichroic pigments described later, thermotropic liquid crystal is preferred. Polymerizable liquid crystal compounds can be monomers or polymers polymerized from dimers or more.

[0054] When the polymerizable liquid crystal compound is a thermotropic liquid crystal, it can be either a thermotropic liquid crystal compound displaying a nematic liquid crystal phase or a thermotropic liquid crystal compound displaying a smectic liquid crystal phase. From the viewpoint of exhibiting high dichroism, the liquid crystal state displayed by the polymerizable liquid crystal compound is preferably a smectic phase, and if it is a higher-order smectic phase, it is even more preferable from the viewpoint of performance enhancement. Among these, higher-order smectic liquid crystal compounds that form smectic B, smectic D, smectic E, smectic F, smectic G, smectic H, smectic I, smectic J, smectic K, or smectic L phases are more preferable, and higher-order smectic liquid crystal compounds that form smectic B, smectic F, or smectic I phases are even more preferable. If the liquid crystal phase formed by the polymerizable liquid crystal is one of these higher-order smectic phases, it is possible to manufacture a polarizing film with higher polarization performance. In addition, such a polarizing film with high polarization performance can produce Bragg peaks originating from higher-order structures such as hexagonal phases and crystalline phases in X-ray diffraction measurements. The Bragg peak originates from the periodic structure of molecular orientation, and films with periodic intervals of 3–6 Å can be obtained. From the viewpoint of obtaining higher polarization characteristics, it is preferable that the polarization film of the present invention comprises a polymer of polymeric liquid crystal oriented in a smectic phase.

[0055] As a polymerizable liquid crystal compound, one type can be used alone, or two or more types can be used in combination. As long as the effect of the present invention is not impaired, the polymerizable liquid crystal composition containing other compounds described later may also contain other polymerizable liquid crystal compounds besides the above-mentioned polymerizable liquid crystal compounds. From the viewpoint of obtaining a polarizing film with high orientation order, the proportion of the above-mentioned polymerizable liquid crystal compound to the total mass of all polymerizable liquid crystal compounds contained in the polymerizable liquid crystal composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0056] Relative to the solid content of the polymeric liquid crystal composition, the content of the polymeric liquid crystal compound in the polarization film forming composition of the present invention is preferably 40 to 99.9% by mass, more preferably 60 to 99% by mass, and even more preferably 70 to 99% by mass. If the content of the polymeric liquid crystal compound is within the above range, there is a tendency for the orientation of the polymeric liquid crystal compound to increase. It should be noted that, in this specification, the solid content refers to the total amount of components after removing the solvent from the polymeric liquid crystal composition.

[0057] <Polarizing film; dichroic pigment>

[0058] Dichroic pigments are pigments that exhibit different absorbance along their long axis and short axis. Preferably, dichroic pigments possess the property of absorbing visible light, and more preferably, they have a maximum absorption wavelength (λMAX) in the range of 380–680 nm. Examples of such dichroic pigments include acridine pigments, oxazine pigments, anthocyanins, naphthalene pigments, azo pigments, and anthraquinone pigments, with azo pigments being the most preferred. Examples of azo pigments include monoazo, diazo, triazo, tetraazo, and pizoazo pigments, with diazo and triazo pigments being the most preferred. Dichroic pigments can be used alone or in combination. To achieve absorption across the entire visible light spectrum, it is preferable to combine two or more dichroic pigments, and more preferably, three or more dichroic pigments.

[0059] As azo dye, for example, compounds of formula (I) (hereinafter, sometimes referred to as "compound (I)") can be cited.

[0060] T1-A1(-N=N-A2)p-N=N-A3-T2(I)

[0061] [In formula (I), A1, A2, and A3 independently represent 1,4-phenylene, naphthalene-1,4-diyl, benzoic acid phenylyl, 4,4'-stilbene, or divalent heterocyclic groups that may have substituents. T1 and T2 are electron-withdrawing or electron-donating groups, positioned substantially 180° relative to the azo bond plane. p represents an integer from 0 to 4. When p is 2 or higher, each A2 may be the same or different from the others. Within the visible absorption range, the -N=N- bond can be replaced by -C=C-, -COO-, -NHCO-, or -N=CH- bonds.]

[0062] From the viewpoint of obtaining good light absorption characteristics, the content of dichroic pigments (the total amount when multiple pigments are included) is typically 1 to 60 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, preferably 1 to 40 parts by mass, and more preferably 1 to 20 parts by mass. If the content of dichroic pigments is less than this range, light absorption becomes insufficient, and adequate polarization performance cannot be obtained; if it is more than this range, it may sometimes hinder the orientation of liquid crystal molecules.

[0063] (First protective layer 180 and second protective layer 190)

[0064] The first protective layer 180 and the second protective layer 190 each have the function of protecting the surface of the linear polarizer 220.

[0065] The first protective layer 180 is laminated onto the linear polarizer 220 via an adhesive layer or bonding agent layer as needed. Alternatively, the first protective layer 180 may be directly laminated to the linear polarizer 220. Here, "direct lamination" includes lamination onto the linear polarizer by means of the self-adhesive property of the first protective layer. To improve adhesion to the linear polarizer, the first protective layer may undergo surface treatment (e.g., corona treatment, etc.) or may be formed as a thin layer such as an undercoat (also known as an easy-to-adhere layer).

[0066] The materials used for the adhesive layer and bonding agent layer between the first protective layer 180 and the linear polarizer 220 are not particularly limited. Examples of adhesives include cured products of curable compositions containing cationic polymeric compounds, as detailed in the section on the first adhesive layer 150 described later, and aqueous adhesives, as detailed in the section on the second adhesive layer 40. Another example of an adhesive is a cured product of a curable composition containing free radical polymeric compounds. Examples of adhesives include acrylic adhesives, urethane adhesives, and silicone adhesives.

[0067] The second protective layer 190 is laminated onto the linear polarizer 220 via the first adhesive layer 150, which will be described later. To improve adhesion to the linear polarizer, the second protective layer may also undergo surface treatment (e.g., corona treatment), or a thin layer such as an undercoat (also known as an easy-to-adhere layer) may be formed. The material of the first adhesive layer 150 between the second protective layer 190 and the linear polarizer 220 will be described later.

[0068] As the first and second protective layers, resin films with excellent properties such as transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, and tensile strength can be used. The resin film can be a thermoplastic resin film. Specific examples of such resins include: cellulose-based resins such as triacetyl cellulose; polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone-based resins; polysulfone-based resins; polycarbonate-based resins; polyamide-based resins such as nylon and aromatic polyamides; polyimide-based resins; polyolefin-based resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin-based resins having cyclic and norbornene structures (also called norbornene-based resins); (meth)acrylic resins such as polymethyl methacrylate; polyarylate-based resins; polystyrene-based resins; polyvinyl alcohol-based resins; and mixtures thereof. Protective films made of this material are readily available on the market. In this specification, (meth)acrylic acid refers to either acrylic acid or methacrylic acid.

[0069] The first protective layer is suitable as a cyclic polyolefin resin film, and the second protective layer 190 is suitable as a triacetyl cellulose resin film. By using a cyclic polyolefin resin film, moisture can be prevented from penetrating from the outside. On the other hand, since iodine does not permeate the interior of the cyclic polyolefin resin film, when the first protective layer is a cyclic polyolefin resin film, iodine in the polarizer is difficult to diffuse outside the polarizer and remains inside, easily causing hydrolysis of the triacetyl cellulose resin film of the second protective layer. In this disclosure, even with the above-described configuration, the hydrolysis of the triacetyl cellulose resin film is suppressed, resulting in the suppression of cracks.

[0070] The thickness of the thermoplastic resin film is preferably 0.1 μm to 60 μm, more preferably 0.5 μm to 50 μm, and even more preferably 1 μm to 40 μm. In particular, the thickness of the second protective layer 190 is suitable to be 35 μm or less, and can be 30 μm or less.

[0071] Surface treatments such as hard coating, anti-reflective treatment, anti-sticking treatment, and anti-glare treatment can be applied to the thermoplastic resin film as needed. Further / or, the thermoplastic resin film can be treated to improve visibility when viewed through polarized sunglasses (typically by imparting (ellipsoidal) polarization or ultra-high phase difference). By implementing such treatments, excellent visibility can be achieved even when viewing the display image through polarized lenses such as polarized sunglasses. Therefore, polarizing plates with phase difference layers are also suitable for use in image display devices that can be used outdoors.

[0072] Thermoplastic resin films can be produced by stretching a film containing the aforementioned thermoplastic resin. Examples of stretching processes include uniaxial stretching and biaxial stretching. Examples of stretching directions include: the mechanical flow direction (MD) of the unstretched film, a direction orthogonal to it (TD), and a direction oblique to the mechanical flow direction (MD). Biaxial stretching can be simultaneous biaxial stretching in two stretching directions, or sequential biaxial stretching where the film is stretched in one direction followed by stretching in another. The stretching process can be performed, for example, by using two or more pairs of clamping rollers with increased circumferential speed on the exit side to stretch along the length direction (mechanical flow direction: MD), or by using a chuck to hold both ends of the unstretched film and extending it along a direction orthogonal to the mechanical flow direction (TD). In this case, the phase difference value and wavelength dispersion can be controlled by adjusting the film thickness or the stretching ratio. Furthermore, the wavelength dispersion value can be controlled by adding a wavelength dispersion modifier to the resin.

[0073] The aforementioned thermoplastic resin film may contain any appropriate additives depending on the intended purpose. Examples of additives include: antioxidants, light stabilizers, UV absorbers, weather stabilizers, and heat stabilizers (such as hindered phenolic, phosphorus, and sulfur-based compounds); reinforcing materials such as glass fiber and carbon fiber; near-infrared absorbers; flame retardants such as tris(dibromopropyl) phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic and inorganic fillers; resin modifiers; plasticizers; lubricants; and phase difference reducers. The types, combinations, and amounts of these additives can be appropriately determined based on the intended purpose and desired properties.

[0074] In addition, to impart desired surface optical properties or other characteristics, a coating layer (surface treatment layer) can be formed on the outer surface of the thermoplastic resin film. Specific examples of surface treatment layers include hard coatings, anti-glare layers, anti-reflective layers, antistatic layers, and antifouling layers. There are no particular limitations on the method of forming the surface treatment layer; known methods can be used. The surface treatment layer can be formed on one side or both sides of the thermoplastic resin film.

[0075] [Hard coating]

[0076] The hard coating has the function of increasing the surface hardness of the thermoplastic resin film and is designed to prevent surface scratches, etc. Preferably, the hard coating has a pencil hardness of H or higher as determined by the pencil hardness test (the optical film with the hard coating is placed on a glass plate) as specified in JIS K 5600-5-4:1999 "General Test Methods for Coatings - Part 5: Mechanical Properties of Coatings - Section 4: Scratch Hardness (Pencil Method)".

[0077] Materials forming hard coatings are typically materials that cure by heat or light. Examples include organic hard coating materials such as silicone-based, melamine-based, epoxy-based, (meth)acrylate-based, and urethane (meth)acrylate-based materials, as well as inorganic hard coating materials such as silica. Among these, urethane (meth)acrylate-based or multifunctional (meth)acrylate-based hard coating materials are preferred for their good adhesion to thermoplastic resin films and high productivity. In this specification, (meth)acrylate refers to any of the following: acrylate or methacrylate.

[0078] To achieve desired effects such as adjusting refractive index, increasing flexural modulus, stabilizing volume shrinkage, and even improving heat resistance, antistatic properties, and anti-glare properties, hard coatings can contain various fillers. Additionally, hard coatings may also contain additives such as antioxidants, UV absorbers, light stabilizers, antistatic agents, leveling agents, and defoamers.

[0079] To further improve strength, the hard coating may contain additives. The additives are not limited and may include inorganic microparticles, organic microparticles, or mixtures thereof. Furthermore, for optimal hardness, a thicker hard coating is preferable; however, if it is too thick, it is prone to cracking during cutting. Therefore, the thickness can range from 1 μm to 20 μm, or from 2 μm to 10 μm. The preferred thickness of the hard coating is 3 μm to 7 μm.

[0080] The anti-glare layer is a layer with a finely textured surface, preferably formed using the aforementioned hard coating material.

[0081] An anti-glare layer with a finely textured surface can be formed in the following ways: 1) forming a coating containing microparticles on a stretch film and setting a texture based on the microparticles; 2) forming a coating containing microparticles or not on a stretch film and then pressing it onto a mold (roller, etc.) with a textured surface to transfer the textured shape (also known as embossing).

[0082] An anti-reflective layer is a layer used by observers of thermoplastic resin films to reduce the reflection of external light from the film's surface, typically with a reflectivity of less than 1.5% for visible light. Such an anti-reflective layer is typically obtained by laminating a high-refractive-index layer with a high refractive index and a low-refractive-index layer, or by using the methods and materials described in Japanese Patent Application Laid-Open No. 2021-6929. By adjusting these refractive indices and the thickness of each layer, reflected light from each layer can be mutually weakened, resulting in excellent anti-reflective properties.

[0083] As will be described in detail later, antireflective layers comprising high-refractive-index and low-refractive-index layers are preferred because manufacturing them using a coating-type composition capable of forming both layers separately is extremely simple. Here, an example of a coating-type composition capable of forming both high-refractive-index and low-refractive-index layers is given. This coating-type composition is liquid and contains a suitable curable resin and, as needed, additives. The coating-type composition capable of forming the high-refractive-index layer (composition for forming the high-refractive-index layer) is, for example, prepared by dissolving a curable resin such as urethane acrylate with an initiator for photopolymerization (photopolymerization initiator) such as acetophenone, benzophenone, benzoyl dimethyl ketal, α-hydroxyalkylphenyl ketone, α-aminoalkylphenyl ketone, or thioxanthone in a solvent such as methyl ethyl ketone or methyl isobutyl ketone. To improve coatability, a leveling agent may be included, preferably a fluorinated leveling agent. Furthermore, as a coating composition capable of forming a low-refractive-index layer (composition for forming a low-refractive-index layer), it is prepared by dispersing silica particles in a solution of an initiator for photopolymerization (photopolymerization initiator) such as acetophenone, benzophenone, benzoyldimethyl ketal, α-hydroxyalkylphenyl ketone, α-aminoalkylphenyl ketone, or thioxanthone in a solvent such as 1-methoxy-2-propyl acetate or methyl isobutyl ketone, in an adhesive resin such as polyethylene glycol diacrylate or pentaerythritol (tri / tetra) acrylate, which serves as a curing resin. To improve coatability, a fluorinated leveling agent may be included. It should be noted that the coating compositions listed here capable of forming both high-refractive-index and low-refractive-index layers are merely examples; it is preferable to optimize the high-refractive-index layer forming composition and the low-refractive-index layer forming composition separately according to the characteristics of the desired antireflective layer.

[0084] The anti-reflective layer may, for example, have a low refractive index layer. Alternatively, it may be a multilayer structure in which a high refractive index layer and / or a medium refractive index layer are further provided between the thermoplastic resin film and the low refractive index layer.

[0085] A low-refractive-index layer can be formed by applying a coating liquid containing a cured resin, a transparent resin such as a metal alkoxide polymer, and inorganic particles, followed by curing the coating layer as needed. Examples of inorganic particles include low-refractive-index particles such as LiF (refractive index 1.4), MgF (refractive index 1.4), 3NaF·AlF (refractive index 1.4), AlF (refractive index 1.4), Na3AlF6 (refractive index 1.33), and hollow silica particles.

[0086] An antistatic layer is provided for purposes such as imparting conductivity to the surface of a thermoplastic resin film and suppressing the effects caused by static electricity. The antistatic layer can be formed, for example, by coating a resin composition containing a conductive substance (antistatic agent) onto the thermoplastic resin film. For instance, by coexisting the antistatic agent with the hard coating material used in the formation of the aforementioned hard coating layer, an antistatic hard coating layer can be formed.

[0087] An antifouling layer is designed to impart properties such as hydrophobicity, oleophobicity, sweat resistance, and stain resistance. Suitable materials for forming the antifouling layer are fluorinated organic compounds. Examples of fluorinated organic compounds include fluorocarbons, perfluorosilanes, and their polymeric compounds. The method for forming the antifouling layer can vary depending on the material being formed, employing methods such as physical vapor deposition (PVD), chemical vapor deposition (CVD), and wet coating, exemplified by evaporation and sputtering. The average thickness of the antifouling layer is typically around 1–50 nm, preferably 3–35 nm.

[0088] When the first protective layer is a resin layer such as a thermoplastic resin layer or a cured resin layer as described later, the linear polarizer and the first protective layer can be directly bonded without an adhesive layer or bonding agent layer.

[0089] For example, a composition containing a thermoplastic resin is coated onto a support substrate and dried as needed to obtain a thermoplastic resin layer with a support substrate. This thermoplastic resin layer with a support substrate is then bonded to a linear polarizer via an adhesive layer or bonding agent layer as needed. The support substrate is then peeled off, thereby allowing a thermoplastic resin layer as a first protective layer to be laminated onto the linear polarizer (Method 1). For example, if the first protective layer is a thermoplastic resin layer, the above composition can also be directly coated onto the surface of the linear polarizer and dried as needed to form a thermoplastic resin layer. In this case, the linear polarizer is directly bonded to the first protective layer without an adhesive layer or bonding agent layer (Method 2). However, if the composition contains a solvent, Method 1 is preferred from the perspective of easily and stably forming a thermoplastic resin layer with a sufficiently reduced solvent content.

[0090] The first protective layer can be a cured resin layer containing a cured product of a curable resin. Examples of curable resins include thermosetting resins and active energy curable resins, such as (meth)acrylate resins, epoxy resins, oxetane resins, urethane resins, (meth)acrylate urethane resins, and melamine resins. The cured resin layer containing the cured product of the curable resin can be formed by coating a composition containing the curable resin onto a support substrate, drying it as needed, and then heating or irradiating it with active energy rays such as visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, gamma rays, or electron beams. The resulting cured resin layer with the support substrate is then bonded to a linear polarizer via an adhesive layer as needed, and the support substrate is then peeled off, thereby allowing the cured resin layer serving as the first protective layer to be laminated onto the linear polarizer.

[0091] (First adhesive layer 150)

[0092] The first adhesive layer 150 adheres the linear polarizer 220 to the second protective layer 190.

[0093] The first adhesive layer 150 can be in direct contact with the linear polarizer 220. When the linear polarizer 220 has an alignment film on the side of the first liquid crystal phase difference layer 30, it can also be in direct contact with the alignment film of the linear polarizer 220.

[0094] The first adhesive layer 150 is in direct contact with the second protective layer 190.

[0095] The thickness of the first adhesive layer 150 can be 0.5–5.0 μm, preferably 1.0–4.0 μm, and more preferably 1.2–2.5 μm. The thickness of the first adhesive layer 150 is most preferably 1.6–2.1 μm. By appropriately adjusting the thickness range, the reduction of the second protective layer can be suppressed, thereby suppressing cracking.

[0096] (Material of the first adhesive layer)

[0097] The first adhesive layer is a cured layer of a curable composition containing a cationic polymeric compound.

[0098] (Curing composition)

[0099] The curable composition contains a cationic polymeric compound.

[0100] (Catonic polymeric compounds)

[0101] Cationic polymerizable compounds are compounds or oligomers that are solidified by cationic polymerization reactions through irradiation or heating with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Specifically, examples include epoxy compounds, oxetane compounds, and vinyl compounds.

[0102] (Epoxy compounds)

[0103] Epoxy compounds are compounds with one or more epoxy groups, such as alicyclic epoxy compounds, aliphatic epoxy compounds, and aromatic epoxy compounds.

[0104] (Alicyclic epoxides)

[0105] Alicyclic epoxy compounds are compounds having one or more alicyclic epoxy groups. In this specification, an alicyclic epoxy group refers to functional group A having an aliphatic ring and a three-membered ring (ethylene oxide ring) formed by two adjacent carbon and oxygen atoms forming the aforementioned aliphatic ring. Functional group A can be obtained by removing (CH2) from a compound of formula (a). m Functional groups are obtained by using any hydrogen atom in the group. m is an integer from 2 to 5, preferably m is 4.

[0106]

Chemical Formula 1

[0107]

[0108] In formula (a), (CH2) m Any hydrogen atom in it can be replaced by a straight-chain alkyl group (with 6 or fewer carbon atoms) such as methyl or ethyl.

[0109] Alicyclic epoxides can contain one or more epoxy groups of other structures in the same molecule if the molecule contains at least one functional group A. An example of functional group A is 3,4-epoxycyclohexyl. Alicyclic epoxides can have aromatic rings, but it is preferable that they do not.

[0110] Alicyclic epoxides can be monofunctional alicyclic epoxides having only one functional group A, but polyfunctional alicyclic epoxides containing two or more functional groups A are suitable. Alicyclic epoxides can further have epoxy groups other than alicyclic epoxy groups.

[0111] Specific examples of alicyclic epoxy compounds include 3,4-epoxycyclohexanecarboxylic acid methyl 3,4-epoxycyclohexyl ester, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-1-methyl-4-(1-methylepoxyethyl)cyclohexane, 3,4-epoxycyclohexyl methacrylate, 4-(1,2-epoxyethyl)-1,2-epoxycyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, ethylene bis(3,4-epoxycyclohexanecarboxylate), oxydiethylene bis(3,4-epoxycyclohexanecarboxylate), 1,4-cyclohexanedimethylbis(3,4-epoxycyclohexanecarboxylate), and 3-(3,4-epoxycyclohexylmethoxycarbonyl)propyl 3,4-epoxycyclohexanecarboxylic acid, etc.

[0112] Among alicyclic epoxy compounds, methyl 3,4-epoxycyclohexanecarboxylate is preferred from the perspective of having moderate curability and being relatively inexpensive to use.

[0113] As an alicyclic epoxy compound, one type of alicyclic epoxy compound can be used alone, or multiple different types can be used in combination.

[0114] (Aliphatic epoxy compounds)

[0115] Aliphatic epoxides are compounds in which one of the two carbon atoms in the epoxide group is bonded to a carbon atom that constitutes another aliphatic hydrocarbon chain. Aliphatic hydrocarbon chains can have ether bonds or ester bonds.

[0116] It should be noted that alicyclic epoxides, i.e., substances containing functional group A as the alicyclic epoxide group, are excluded from aliphatic epoxides. Aliphatic epoxides can have aromatic rings, but it is preferable that they do not.

[0117] Aliphatic epoxy compounds can be monofunctional aliphatic epoxy compounds having only one of the above-mentioned epoxy groups, but polyfunctional aliphatic epoxy compounds containing two or more of the above-mentioned epoxy groups are suitable.

[0118] Examples of monofunctional aliphatic epoxy compounds include glycidyl ethers of aliphatic alcohols and glycidyl esters of alkyl carboxylic acids. Specific examples include allyl glycidyl ether, butyl glycidyl ether, sec-butylphenyl glycidyl ether, 2-ethylhexyl glycidyl ether, mixed alkyl glycidyl ethers with 12 and 13 carbon atoms, glycidyl ethers of alcohols, monoglycidyl ethers of higher aliphatic alcohols, and glycidyl esters of higher fatty acids. As monofunctional aliphatic epoxy compounds, a single monofunctional epoxy compound can be used alone, or multiple different monofunctional epoxy compounds can be used in combination.

[0119] Multifunctional aliphatic epoxy compounds have two or more of the aforementioned epoxy groups. An example of a multifunctional aliphatic epoxy compound is the aliphatic diester shown in formula (b) below.

[0120] [Chemical Formula 2]

[0121]

[0122] In formula (b), Z is an alkyl group with 1 to 9 carbon atoms, an alkylidene group with 3 or 4 carbon atoms, a divalent alicyclic hydrocarbon group, or a group of the formula -C m H 2m -Z1-C n H 2n - The divalent group shown. Additionally, the above formula -C m H 2m -Z1-C n H 2n In the given string, -Z1- represents -O-, -CO-O-, -O-CO-, -SO2-, -SO-, or CO-, m and n each independently represent integers greater than or equal to 1, and the sum of m and n is less than or equal to 9.

[0123] The divalent alicyclic hydrocarbon group can be, for example, a divalent alicyclic hydrocarbon group with 4 to 8 carbon atoms, such as the divalent group shown in formula (b-1) below.

[0124]

Chemical Formula 3

[0125]

[0126] Specific examples of compounds shown in formula (b) include diglycidyl ethers of alkyl diols, diglycidyl ethers of oligoalkylene diols with repeats up to about 4, or diglycidyl ethers of alicyclic diols.

[0127] Examples of glycols capable of forming compounds as shown in formula (b) above include ethylene glycol, propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-2,4-pentanediol, 2,4-pentanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 3,5-heptanediol, 1,8-octanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, etc.; oligomeric alkylene glycols such as diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, etc.; and alicyclic glycols such as cyclohexanediol, cyclohexanediol, etc.

[0128] From the viewpoint of obtaining a first-active-energy ray-curable composition with low viscosity and easy coating, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether are preferred. As aliphatic epoxy compounds, a single aliphatic epoxy compound can be used, or multiple different compounds can be used in combination.

[0129] Multifunctional aliphatic epoxy compounds can have functional group B in which the epoxy group is bonded to the alicyclic ring via a single bond. Examples of such compounds are those with the following formula.

[0130] [Chemical Formula 4]

[0131]

[0132] In formula (II), R' is a group obtained by removing p -OH groups from a p-hydrone alcohol, and p and n represent natural numbers. Examples of p-hydrone alcohols [R'-(OH)p] include polyols such as 2,2-bis(hydroxymethyl)-1-butanol (alcohols with 1 to 15 carbon atoms). p is preferably 1 to 6, and n is preferably 1 to 30. When p is 1, n is 2 or more. When p is 2 or more, n in each group within parentheses can be the same or different. Specifically, examples of the above compounds include the 1,2-epoxy-4-(2-epoxyethylene)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (trade name "EHPE3150", manufactured by Daicel).

[0133] (Aromatic epoxy compounds)

[0134] Aromatic epoxy compounds refer to compounds in which a glycidyl ether group or a glycidyl ester group is directly bonded to an aromatic ring. Aromatic epoxy compounds can be monofunctional aromatic epoxy compounds with one epoxy group, or polyfunctional aromatic epoxy compounds with two or more epoxy groups. However, the aromatic epoxy compounds described in this specification do not include compounds with an alicyclic epoxy group (functional group A) within the molecule.

[0135] Examples of monofunctional aromatic epoxy compounds include monoglycidyl ethers of monohydric phenols such as phenol, cresol, and butylphenol, or bisphenol derivatives such as bisphenol A and bisphenol F, or their epoxide alkyl adducts; epoxy phenolic resins; monoglycidyl ethers of aromatic compounds with two or more phenolic hydroxyl groups such as resorcinol, hydroquinone, and catechol; monoglycidyl ethers of aromatic compounds with two or more alcoholic hydroxyl groups such as benzenediethanol, benzenediethanol, and dibutyl phthalate; monoglycidyl esters of polycarboxylic acid aromatic compounds with two or more carboxyl groups such as phthalic acid, terephthalic acid, and trimellitic acid; and monoglycidyl esters of benzoic acid, toluene, and naphtholic acid.

[0136] Monofunctional aromatic epoxy compounds can be commercially available, such as "EX-142", "EX-146", "EX-147", and "EX-121" (all manufactured by Nagase ChemteX Co., Ltd.).

[0137] Specific examples of polyfunctional aromatic epoxy compounds include: polyglycidyl ethers of naphthalene or naphthalene derivatives (also known as "naphthalene-type epoxy compounds"); polyglycidyl ethers of bisphenol derivatives such as bisphenol A and bisphenol F (also known as "bisphenol A-type epoxy compounds" and "bisphenol F-type epoxy compounds"); epoxy phenolic resins; polyglycidyl ethers of aromatic compounds with two or more phenolic hydroxyl groups such as resorcinol, hydroquinone, and catechol; polyglycidyl ethers of aromatic compounds with two or more alcoholic hydroxyl groups such as benzenediethanol, benzenediethanol, and dibutyl phthalate; polyglycidyl esters of polycarboxylic acid aromatic compounds with two or more carboxyl groups such as phthalic acid, terephthalic acid, and trimellitic acid; glycidyl esters of benzoic acid, toluene, and naphthoic acid; and styrene oxides or diepoxides of divinylbenzene, such as styrene oxide, alkylated styrene oxide, and vinylnaphthalene epoxides. As a multifunctional aromatic epoxy compound, it can be used alone or in combination with multiple different compounds.

[0138] Commercially available multifunctional aromatic epoxy compounds include, for example, "DENACOL EX-201", "DENACOL EX-711" and "DENACOL EX-721" (all manufactured by Nagase ChemteX Co., Ltd.); "OGSOLEG-280" and "OGSOL CG-400" (both manufactured by Osaka Gas Chemical Co., Ltd.); "EXA-80CRP" and "HP4032D" (both manufactured by DIC Co., Ltd.); "jER828" and "jER828EL" (both manufactured by Mitsubishi Chemical Co., Ltd.); "ADEKA RESIN EP-4100", "ADEKA RESIN EP-4100G", "ADEKA RESIN EP-4100E", "ADEKA RESIN EP-4100L", "ADEKA RESIN EP-4100TX", and "ADEKA RESIN EP-4100G". "EP-4000", "ADEKA RESIN EP-4005", "ADEKA RESIN EP-4901", "ADEKA RESIN EP-4901E" (all of which are manufactured by ADEKA Co., Ltd.), etc.

[0139] (Oxycyclic butane compounds)

[0140] Oxycyclic butane compounds are compounds containing an oxycyclic butyl group, and can be aliphatic, alicyclic, or aromatic compounds. In this specification, oxycyclic butane compounds are defined as compounds that do not have an ethylene oxide ring (epoxy group).

[0141] Oxycyclic butane compounds can be monofunctional oxycyclic butane compounds having only one oxycyclic butyl group, or polyfunctional oxycyclic butane compounds having two or more oxycyclic butyl groups.

[0142] The oxecyclobutane compound is preferably a multifunctional oxecyclobutane compound, and more preferably a difunctional oxecyclobutane compound having two oxecyclobutyl groups.

[0143] Oxycyclic butane compounds include 3,7-bis(3-oxetane)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetane-butylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetane-butylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetane-butylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetane-butylmethyl) ether, triethylene glycol bis(3-ethyl-3-oxetane-butylmethyl) ether, tetraethylene glycol bis(3-ethyl-3-oxetane-butylmethyl) ether, and 1,4-bis(3-ethyl-3-oxetane-butylmethyl)propane. Examples of specific examples include 1,6-bis(3-ethyl-3-oxetane-3-oxetane-3-methoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-[(benzyloxy)methyl]-3-ethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, and xylene-3-oxetane.

[0144] As an oxetane compound, one type of oxetane compound can be used alone, or multiple different compounds can be used in combination.

[0145] Preferably, it is selected from at least one of 3-ethyl-3-hydroxymethyloxetane, phenylenedimethyldioxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and 3-ethyl-3-(cyclohexyloxymethyl)oxetane.

[0146] (Composition of cationic polymeric compounds)

[0147] Cationic polymerizable compounds are suitable for containing alicyclic epoxides.

[0148] The total amount of the cationic polymerizable compound is set at 100 parts by mass. The cationic polymerizable compound preferably contains 10 or more parts by mass of an alicyclic epoxy compound, which can be 20 or more parts by mass, 25 or more parts by mass, or 30 or more parts by mass. There is no particular upper limit on the amount of the alicyclic epoxy compound in the cationic polymerizable compound; it can be less than 90 parts by mass, less than 80 parts by mass, less than 70 parts by mass, less than 60 parts by mass, or less than 50 parts by mass.

[0149] The total amount of the cationic polymerizable compound is set at 100 parts by mass. The cationic polymerizable compound preferably contains 10 parts by mass or more of a multifunctional alicyclic epoxy compound, which can be 20 parts by mass or more, 25 parts by mass or more, or 30 parts by mass or more. There is no particular upper limit on the amount of the multifunctional alicyclic epoxy compound in the cationic polymerizable compound; it can be 90 parts by mass or less, 80 parts by mass or less, 70 parts by mass or less, 60 parts by mass or less, or 50 parts by mass or less.

[0150] By incorporating alicyclic epoxy compounds into cationic polymeric compounds, the crosslinking density is increased, thus creating a trend that can further reduce cracking under high temperature and high humidity conditions and inhibit the disappearance of dichroic pigments such as iodine.

[0151] In addition, if the amount of alicyclic epoxy compounds is too large, they may sometimes react with dichroic pigments such as iodine.

[0152] Cationic polymerizable compounds are suitable for containing oxobutane compounds.

[0153] The total mass of the cationic polymerizable compound is set at 100 parts by mass. The cationic polymerizable compound preferably contains 10 or more parts by mass of an oxetane compound, which can be 20 or more parts by mass, 30 or more parts by mass, 40 or more parts by mass, 45 or more parts by mass, or 50 or more parts by mass. There is no particular upper limit to the content of the oxetane compound in the cationic polymerizable compound; it can be less than 90 parts by mass, or less than 85 parts by mass, 80 parts by mass, 75 parts by mass, 70 parts by mass, 60 parts by mass, or 50 parts by mass.

[0154] The total mass of the cationic polymerizable compound is set at 100 parts by mass. The cationic polymerizable compound preferably contains 10 parts by mass or more of a multifunctional oxetane compound, which can be 20 parts by mass or more, 30 parts by mass or more, 40 parts by mass or more, 45 parts by mass or more, or 50 parts by mass or more. There is no particular upper limit to the content of the multifunctional oxetane compound in the cationic polymerizable compound; it can be 90 parts by mass or less, or 85 parts by mass or less, 80 parts by mass or less, 75 parts by mass or less, 70 parts by mass or less, 60 parts by mass or less, or 50 parts by mass or less.

[0155] By incorporating oxobutane compounds into cationic polymerizable compounds, the crosslinking density is further increased, thus creating a trend that can further reduce cracking under high temperature and high humidity conditions and inhibit the disappearance of dichroic pigments such as iodine.

[0156] Cationic polymerizable compounds are also suitable for containing alicyclic epoxides and oxocyclic butanes.

[0157] (Catonic polymerization initiator)

[0158] The curable composition preferably contains a cationic polymerization initiator in addition to a cationic polymerizable compound.

[0159] Cationic polymerization initiators can be either thermal cationic polymerization initiators or photocationic polymerization initiators.

[0160] Photocationic polymerization initiators generate cationic species or Lewis acids through irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, initiating the polymerization reaction of cationic polymerizable compounds. Because photocationic polymerization initiators exert their catalytic effect through photocatalysis, they exhibit excellent storage stability and workability even when mixed with cationic polymerizable compounds. Examples of compounds that can be used as photocationic polymerization initiators and generate cationic species or Lewis acids through irradiation with active energy rays include, for example, aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts, and iron-aromatic complexes. The photocationic polymerization initiator is preferably an ionic compound selected from aromatic sulfonium salts and aromatic iodonium salts.

[0161] Examples of aromatic diazonium salts include benzenediazohexafluoroantimonate, benzenediazohexafluorophosphate, and benzenediazohexafluoroborate.

[0162] Examples of aromatic iodonium salts include diphenyliodonium tetra(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate.

[0163] Examples of aromatic sulfonium salts include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetra(pentafluorophenyl)borate, 4,4'-bis[diphenylsulfonyl]diphenylsulfide bis(hexafluorophosphate), 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]diphenylsulfide bis(hexafluoroantimonate), 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]diphenylsulfide bis(hexafluorophosphate), and 7-[bis(p-toluyl)sulfonyl]... ]-2-Isopropylthioxanthone hexafluoroantimonate, 7-[di(p-toluyl)sulfonyl]-2-isopropylthioxanthone tetra(pentafluorophenyl)borate, 4-phenylcarbonyl-4'-diphenylsulfonyl-diphenyl sulfide hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4'-diphenylsulfonyl-diphenyl sulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4'-di(p-toluyl)sulfonyl-diphenyl sulfide tetra(pentafluorophenyl)borate.

[0164] Examples of iron-aromatic complexes include xylene-cyclopentadienyl iron(II) hexafluoroantimonate, cumene-cyclopentadienyl iron(II) hexafluorophosphate, and xylene-cyclopentadienyl iron(II) tri(trifluoromethanesulfonyl)methane.

[0165] Photocationic polymerization initiators can be used alone or in combination of two or more. Among the above, aromatic sulfonate salts, in particular, exhibit ultraviolet absorption characteristics even in the wavelength region around 300 nm, thus enabling the production of adhesive cured layers with excellent curability, good mechanical strength, and good adhesive strength, and are therefore preferred.

[0166] (Other ingredients)

[0167] Curable compositions may contain additives such as ion traps, antioxidants, chain transfer agents, tackifiers, thermoplastic resins, fillers, flow modifiers, plasticizers, defoamers, antistatic agents, leveling agents, solvents, and photosensitizing agents, as needed.

[0168] (Composition of the curing composition)

[0169] In the curable composition, the cationic polymeric compound may be 50% or more by mass, 60% or more by mass, 70% or more by mass, 80% or more by mass, or 90% or more by mass relative to the total solid content of the curable composition.

[0170] In the curable composition, the content of the cationic polymerization initiator is typically 0.1 to 10 parts by mass relative to 100 parts by mass of the cationic polymerization compound. Two or more cationic polymerization initiators may be included.

[0171] (Adhesion method based on curing composition)

[0172] The bonding of two adhesive layers based on a curable composition can be performed as follows: a curable composition is applied to at least one bonding surface selected from the bonding surfaces of the two layers, the two layers are overlapped by the coating of the curable composition, and then pressed from above and below using a bonding roller or the like, and the curable composition is cured by irradiation with active energy rays, or the adhesive composition is cured by heating, etc.

[0173] Before forming the coating layer of the curable composition, at least one of the bonding surfaces selected from the respective bonding surfaces of the two layers may be subjected to an easy-bonding treatment such as saponification, corona treatment, plasma treatment, primer treatment, anchor coating treatment, etc.

[0174] The coating layer of the curable composition can be formed using various coating methods such as die coating machine, comma coating machine, gravure coating machine, bar coating machine, and doctor blade coating machine.

[0175] The light intensity during irradiation with active energy rays is not particularly limited, but is preferably 10 mW / cm². 2 Above and 1,000 mW / cm 2 The irradiation intensity is preferably within the wavelength range effective for activating the photocationic polymerization initiator. It is preferable to irradiate once or multiple times with such an intensity, so that the cumulative light dose is 10 mJ / cm². 2 The above, more preferably 100 mJ / cm 2 Above and 1,000 mJ / cm 2 the following.

[0176] There are no particular limitations on the light source used for the polymerization and curing of the curable composition. Examples include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, chemical lamps, black lamps, microwave-excited mercury lamps, and metal halide lamps.

[0177] (Phase difference layer stack 300)

[0178] The phase retardation layer stack 300 has, in sequence, a first liquid crystal phase retardation layer 30, a second adhesive layer 40, and a second liquid crystal phase retardation layer 50, starting from the side of the linear polarizer 220.

[0179] (First liquid crystal phase reversal layer 30 and second liquid crystal phase reversal layer 50)

[0180] The liquid crystal phase retardation layer is a cured layer of an oriented polymeric liquid crystal compound that exhibits a phase retardation.

[0181] The liquid crystal phase retardation layer is not limited as long as it exhibits a phase difference in any direction. It can be a phase retardation layer that generates an in-plane phase difference, such as a positive A-plate and a negative A-plate, or a phase retardation layer that generates a phase difference in the thickness direction, such as a positive C-plate and a negative C-plate. Furthermore, the positive A-plate and the negative A-plate can be λ / 4 plates or λ / 2 plates, respectively. Additionally, the liquid crystal phase retardation layer can be tilted or formed in a cholesteric orientation.

[0182] The first liquid crystal phase retardation layer 30 and the second liquid crystal phase retardation layer 50 can each be a single-layer liquid crystal phase retardation layer or a stack of multiple liquid crystal phase retardation layers.

[0183] The angle θ between the slow axis of the first liquid crystal retardation layer 30 and the transmission axis of the linear polarizer 220 is suitable to be 10° to 20° or -10° to -20°. Therefore, when the optical laminate is used in an OLED display device, it effectively suppresses the reflection of external light caused by the metal electrodes.

[0184] Each liquid crystal phase difference layer can be either positive wavelength dispersion or reverse wavelength dispersion.

[0185] When the in-plane phase difference value of the phase difference layer stack 300 for light with wavelength λnm is set as Re(λ), the following relationship (1) and (2) are suitable.

[0186] 80nm≤Re(450)≤130nm (1)

[0187] Re(450) / Re(550)≤1.00 (2)

[0188] [In equations (1) and (2),]

[0189] Re(450) represents the in-plane phase difference in nm for light with a wavelength of 450 nm.

[0190] Re(550) represents the in-plane phase difference in nm for light with a wavelength of 550 nm.

[0191] In this invention, the in-plane phase difference value of the phase difference layer stack 300 is measured in the state of the optical stack 400. It should be noted that when the first protective layer 180 contained in the optical stack 400 has a phase difference, it is necessary to eliminate the phase difference value to measure the value in the optical stack 400 as the in-plane phase difference value of the phase difference layer stack 300.

[0192] The aforementioned in-plane phase difference value can be measured using an in-plane phase difference measuring device such as the KOBRA-WR manufactured by Oji Measurement & Control Co., Ltd.

[0193] The transmittance at 311 nm of the phase difference layer stack 300 is preferably 8% or higher.

[0194] Liquid crystal phase retardation layers are typically formed by coating a liquid crystal phase retardation layer forming composition containing a polymeric liquid crystal compound onto an alignment film formed on a substrate, and then polymerizing and curing the polymeric liquid crystal compound in an aligned state.

[0195] The thickness of the liquid crystal phase retardation layer is typically less than 10 μm, preferably less than 5 μm, and more preferably more than 0.3 μm and less than 3 μm.

[0196] To achieve a high level of anti-reflective performance, the liquid crystal retardation layer preferably has a λ / 4 plate function (i.e., a π / 2 phase difference function) across the entire visible light region. Specifically, a reverse wavelength dispersive λ / 4 layer is preferred, or a combination of two or more liquid crystal retardation layers with different orientations is also preferred. For example, a liquid crystal retardation layer with a λ / 2 plate function (i.e., a π phase difference function) and a liquid crystal retardation layer with a λ / 4 plate function (i.e., a π / 2 phase difference function) can be combined.

[0197] Furthermore, from the viewpoint of being able to compensate for the anti-reflective function in the tilt direction, it is preferable to include a layer (positive C-plate) that is anisotropic in the thickness direction. In addition, each liquid crystal phase difference layer can be tilted or formed in a cholesteric orientation.

[0198] (Combination of the first liquid crystal phase reversal layer and the second liquid crystal phase reversal layer)

[0199] The first and second liquid crystal phase retardation layers can be the same liquid crystal phase retardation layers or combinations of different types of liquid crystal phase retardation layers.

[0200] For example, one of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer can be an inverse wavelength dispersion λ / 4 plate, and the other of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer can be a positive C plate.

[0201] Alternatively, one of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer may be a positive wavelength dispersive λ / 2 plate, and the other of the first liquid crystal phase difference layer and the second liquid crystal phase difference layer may be a positive wavelength dispersive λ / 4 plate.

[0202] The following describes a stack of a reverse wavelength dispersion λ / 4 plate, a positive wavelength dispersion λ / 4 plate, and a positive wavelength dispersion λ / 2 plate, as an example of a liquid crystal phase difference layer, and a positive C plate.

[0203] (Inverse wavelength dispersion λ / 4 plate (R))

[0204] For the inverse wavelength dispersion λ / 4 plate, if the in-plane phase difference of light with respect to wavelength λnm in the entire visible light region is set as Re(λ), then it is preferable to satisfy the optical characteristics shown in equations (R1) and (R2) below, and preferably to satisfy the optical characteristics shown in equations (R1), (R2) below and (R3) below.

[0205] 100nm<Re(550)<160nm…(R1)

[0206] (In the formula, Re(550) represents the in-plane phase difference (in-plane delay) for light with a wavelength of 550 nm.)

[0207] Re(450) / Re(550)≤1.0…(R2)

[0208] 1.00≤Re(650) / Re(550)…(R3)

[0209] (In the formula, Re(450) represents the in-plane phase difference (in nm) for light with a wavelength of 450 nm, Re(550) represents the in-plane phase difference (in nm) for light with a wavelength of 550 nm, and (650) represents the in-plane phase difference (in nm) for light with a wavelength of 650 nm.)

[0210] If the Re(450) / Re(550) ratio of the liquid crystal phase retardation layer exceeds 1.0, the light leakage on the short-wavelength side of the ellipsoid having the liquid crystal phase retardation layer increases. Preferably, it is 0.7 or more and 1.0 or less, more preferably 0.80 or more and 0.95 or less, even more preferably 0.80 or more and 0.92 or less, and particularly preferably 0.82 or more and 0.88 or less.

[0211] The value of “Re(450) / Re(550)” can be arbitrarily adjusted by adjusting the mixing ratio of the polymeric liquid crystal compound, the stacking angle of multiple optical anisotropic layers, and the phase difference.

[0212] The in-plane phase difference value of the liquid crystal phase difference layer can be adjusted by the thickness of the liquid crystal phase difference layer. Since the in-plane phase difference value is determined by the following equation (4), in order to obtain the desired in-plane phase difference value (Re(λ)), Δn(λ) and the film thickness d can be adjusted. The thickness of the liquid crystal phase difference layer is preferably 0.5 μm to 5 μm, more preferably 1 μm to 3 μm. The thickness of the liquid crystal phase difference layer can be measured by an interferometer, a laser microscope or a stylus-type film thickness gauge. It should be noted that Δn(λ) depends on the molecular structure of the polymeric liquid crystal compound described later.

[0213] Re(λ)=d×Δn(λ)…(4)

[0214] (In the formula, Re(λ) represents the in-plane phase difference (nm) at wavelength λnm, d represents the film thickness, and Δn(λ) represents the birefringence at wavelength λnm.)

[0215] A liquid crystal phase retardation layer is typically formed by coating a liquid crystal phase retardation layer forming composition onto an alignment film formed on a substrate, and then polymerizing the polymerizable liquid crystal compound contained in the liquid crystal phase retardation layer composition in an aligned state. Furthermore, the liquid crystal phase retardation layer forming composition may further include solvents, photopolymerization initiators, photosensitizers, polymerization inhibitors, leveling agents, and adhesion enhancers.

[0216] <Polymerizable liquid crystal compound for forming a reverse wavelength dispersive λ / 4 plate>

[0217] Polymerizable liquid crystal compounds refer to liquid crystal compounds having polymerizable groups, especially photopolymerizable groups. Conventionally known polymerizable liquid crystal compounds can be used as polymerizable liquid crystal compounds for forming a reverse wavelength dispersion λ / 4 plate. Photopolymerizable groups refer to groups capable of participating in polymerization reactions through reactive species generated by a photopolymerization initiator, such as active free radicals or acids. Examples of photopolymerizable groups include vinyl, ethoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloxy, ethylene oxide, and oxetyl. Acryloyloxy, methacryloxy, ethoxy, and oxetyl are preferred, with acryloyloxy being more preferred. The liquid crystal can be thermotropic or lyotropic; thermotropic liquid crystals are preferred from the perspective of enabling dense film thickness control. Furthermore, the phase-ordered structure in the thermotropic liquid crystal can be nematic liquid crystal or smectic liquid crystal. Additionally, it can be rod-shaped or disk-shaped liquid crystal. Polymerizable liquid crystal compounds can be used alone or in combination of two or more.

[0218] From the viewpoint of exhibiting reverse wavelength dispersion, liquid crystals with a mesocrystalline structure in a T-shaped or H-shaped form that further exhibit birefringence in a direction perpendicular to the direction of the molecular long axis are preferred as polymerizable liquid crystal compounds. From the viewpoint of obtaining stronger dispersion, T-shaped liquid crystals are more preferred. Specifically, as a structure of T-shaped liquid crystals, for example, compounds shown in the following formula (I) can be cited.

[0219] [Chemical Formula 5]

[0220]

[0221] In formula (I), Ar represents a divalent aromatic group that may have substituents. Preferably, the divalent aromatic group contains at least one of nitrogen, oxygen, or sulfur atoms. When the divalent group Ar contains two or more aromatic groups, these two or more aromatic groups can be bonded to each other via single bonds, -CO-O-, -O-, or other divalent bonding groups.

[0222] G 1 and G 2 Each of these groups independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atom contained in the divalent aromatic group or divalent alicyclic hydrocarbon group may be replaced by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and the carbon atom constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom, or a nitrogen atom.

[0223] L 1 L 2 B 1 and B 2 Each is an independent single bond or a divalent linker.

[0224] k and l each independently represent integers from 0 to 3, satisfying the relation 1 ≤ k + l. Here, in the case where 2 ≤ k + l, B 1 and B 2 G 1 and G 2 They can be the same as each other, or they can be different.

[0225] E 1 and E 2 Each alkadiyl group independently represents a carbon group with 1 to 17 carbon atoms. Here, the hydrogen atoms in the alkadiyl group can be replaced by halogen atoms, and the -CH2- group can be replaced by -O-, -S-, or -COO-. In the case of multiple -O-, -S-, or -COO- groups, they are not adjacent to each other. P 1 and P 2 Each of the following groups represents a polymeric group or a hydrogen atom independently, with at least one being a polymeric group.

[0226] G 1 and G 2Each of the following is preferably 1,4-phenylene diel that can be substituted with at least one substituent selected from halogen atoms and alkyl groups having 1 to 4 carbon atoms, or 1,4-cyclohexane diel that can be substituted with at least one substituent selected from halogen atoms and alkyl groups having 1 to 4 carbon atoms; more preferably methyl-substituted 1,4-phenylene diel, unsubstituted 1,4-phenylene diel, or unsubstituted 1,4-trans-cyclohexane diel; and particularly preferably unsubstituted 1,4-phenylene diel or unsubstituted 1,4-trans-cyclohexane diel.

[0227] In addition, it is preferable that there are multiple Gs. 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably it is with L 1 or L 2 bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.

[0228] L 1 and L 2 Each is preferably a single bond, an alkylene group having 1 to 4 carbon atoms, and a -O-, -S-, or -R bond. a1 OR a2 -, -R a3 COOR a4 -、-R a5 OCOR a6 -, -R a7 OC=OOR a8 -、-N=N-、-CR c =CR d - or -C≡C-. Here, R a1 ~R a8 Each independently represents a single bond, or an alkylene group having 1 to 4 carbon atoms, R c and R d This indicates an alkyl group or hydrogen atom with 1 to 4 carbon atoms. L 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 - or -OCOR a6-1 — Here, R a2-1 R a4-1 R a6-1 Each can independently represent any one of the following: a single bond, -CH2-, or -CH2CH2-. L 1 and L 2 Each of these can be further preferred independently as a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.

[0229] B 1 and B 2 Each is preferably a single bond, an alkylene group having 1 to 4 carbon atoms, and a -O-, -S-, or -R bond. a9 OR a10 -, -R a11 COOR a12 -, -R a13 OCOR a14 - or -R a15 OC=OOR a16 — Here, R a9 ~R a16 Each can independently represent a single bond or an alkylene group having 1 to 4 carbon atoms. B 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 - or -OCOR a14-1 — Here, R a10-1 R a12-1 R a14-1 Each can independently represent any one of the following: a single bond, -CH2-, or -CH2CH2-. B 1 and B 2 Each of these can be further preferred independently as a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.

[0230] From the viewpoint of exhibiting inverse wavelength dispersion, k and l are preferably in the range of 2 ≤ k + l ≤ 6, preferably k + l = 4, and more preferably k = 2 and l = 2. If k = 2 and l = 2, it becomes a symmetrical structure, which is therefore preferred.

[0231] E 1 and E 2 Alkadiyl groups with 1 to 17 carbon atoms are preferred, and alkadiyl groups with 4 to 12 carbon atoms are more preferred.

[0232] As P 1 or P 2 Examples of polymerizable groups include epoxy, vinyl, ethoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, ethylene oxide, and oxetyl. Acryloyloxy, methacryloyloxy, ethoxy, and oxetyl are preferred, and acryloyloxy is more preferred.

[0233] Ar preferably has at least one selected from aromatic hydrocarbon rings that may have substituents, aromatic heterocycles that may have substituents, and electron-withdrawing groups. Examples of such aromatic hydrocarbon rings include benzene rings, naphthyl rings, and anthracene rings, with benzene rings and naphthyl rings being preferred. Examples of such aromatic heterocycles include furan rings, benzofuran rings, pyrrole rings, indole rings, thiophene rings, benzothiophene rings, pyridine rings, pyrazine rings, pyrimidine rings, triazole rings, triazine rings, pyrrolidine rings, imidazole rings, pyrazole rings, thiazole rings, benzothiazole rings, thienothiazole rings, oxazole rings, benzoxazole rings, and phenanthroline rings. Among these, a thiazole ring, a benzothiazole ring, or a benzofuran ring is preferred, and a benzothiazole ring is even more preferred. Furthermore, when Ar contains a nitrogen atom, this nitrogen atom preferably has π electrons.

[0234] In formula (I), N represents the total number of π electrons contained in the divalent aromatic group represented by Ar. π Preferably, the value is 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Furthermore, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.

[0235] As an aromatic group represented by Ar, the following groups can be suitably listed, for example.

[0236]

Chemical Formula 6

[0237]

[0238] In equations (Ar-1) to (Ar-23), * indicates a connecting part, and Z 0 Z 1 and Z 2 Each can independently represent a hydrogen atom, a halogen atom, an alkyl group with 1 to 12 carbon atoms, a cyano group, a nitro group, an alkyl sulfinyl group with 1 to 12 carbon atoms, an alkyl sulfonyl group with 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group with 1 to 12 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, an alkyl thio group with 1 to 12 carbon atoms, an N-alkylamino group with 1 to 12 carbon atoms, an N,N-dialkylamino group with 2 to 12 carbon atoms, an N-alkylaminosulfonyl group with 1 to 12 carbon atoms, or an N,N-dialkylaminosulfonyl group with 2 to 12 carbon atoms.

[0239] Q 1 and Q 2 Each is represented independently – CR 2’ R 3’ -, -S-, -NH-, -NR 2’ -, -CO- or -O-, R 2’ and R 3’ Each can be independently represented as an alkyl group having 1 to 4 hydrogen atoms or carbon atoms.

[0240] J1 and J 2 Each can be used to represent a carbon atom or a nitrogen atom independently.

[0241] Y 1 and Y 2 Each can be independently represented by an aromatic hydrocarbon group or an aromatic heterocyclic group that can be substituted.

[0242] W 1 and W 2 Each can independently represent a hydrogen atom, cyano group, methyl group, or halogen atom, and m represents an integer from 0 to 6.

[0243] As Y 1 and Y 2 The aromatic hydrocarbon group in the form of the aromatic hydrocarbon group can include phenyl, naphthyl, anthraceneyl, phenanthryl, biphenyl, etc., which have 6 to 20 carbon atoms, with phenyl and naphthyl being preferred, and phenyl being more preferred. As an aromatic heterocyclic group, the form of the aromatic heterocyclic group can include furanyl, pyrroleyl, thiopheneyl, pyridinyl, thiazolyl, benzothiazolyl, etc., which have 4 to 20 carbon atoms and contain at least one heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom, with furanyl, thiopheneyl, pyridinyl, thiazolyl, and benzothiazolyl being preferred.

[0244] Y 1 and Y 2 Each can be independently a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. A polycyclic aromatic hydrocarbon group refers to a fused polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. A polycyclic aromatic heterocyclic group refers to a fused polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0245] Z 0 Z 1 and Z 2 Each of the following is preferably composed of a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 Further preferred are hydrogen atoms, alkyl groups having 1 to 12 carbon atoms, and cyano groups, Z. 1 and Z 2 Further preferred are hydrogen atoms, fluorine atoms, chlorine atoms, methyl groups, and cyano groups.

[0246] Q 1 and Q 2 Preferred NH-, S-, NR 2’ -、-O-,R 2’ Hydrogen atoms are preferred. Among them, -S-, -O-, and -NH- are particularly preferred.

[0247] From the perspective of molecular stability, formulas (Ar-6) and (Ar-7) are preferred among formulas (Ar-1) to (Ar-23).

[0248] In formula (Ar-16) ~ (Ar-23), Y 1 It can bond with the nitrogen atom and Z 0 Together, they form an aromatic heterocyclic group. Examples of aromatic heterocyclic groups that Ar can possess, as described previously, include pyrrole rings, imidazole rings, pyrrololine rings, pyridine rings, pyrazine rings, pyrimidine rings, indole rings, quinoline rings, isoquinoline rings, purine rings, and pyrrolidine rings. This aromatic heterocyclic group may have substituents. Additionally, Y... 1 It can bond with the nitrogen atom and Z 0 Together, these are the aforementioned substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups. Examples include benzofuran rings, benzothiazole rings, and benzoxazole rings.

[0249] Among polymerizable liquid crystal compounds, those with a maximum absorption wavelength of 300–400 nm are preferred. When a photopolymerization initiator is included in the polymerizable liquid crystal composition, polymerization and gelation of the polymerizable liquid crystal compound may occur during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound is 300–400 nm, the generation of reactive species from the photopolymerization initiator and the polymerization and gelation of the polymerizable liquid crystal compound caused by these reactive species can be effectively suppressed even when exposed to ultraviolet light during storage. Therefore, this is advantageous in terms of the long-term stability of the polymerizable liquid crystal composition, and can improve the orientation and uniformity of the resulting cured liquid crystal film. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using a UV-Vis spectrophotometer in a solvent. This solvent is one capable of dissolving the polymerizable liquid crystal compound, such as chloroform.

[0250] Relative to 100 parts by weight of the solid component of the polymeric liquid crystal composition, the content of the polymeric liquid crystal compound in the polymeric liquid crystal composition is, for example, 70 to 99.5 parts by weight, preferably 80 to 99 parts by weight, more preferably 85 to 98 parts by weight, and even more preferably 90 to 95 parts by weight. If the content of the polymeric liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the resulting liquid crystal cured film. It should be noted that, in this specification, the solid component of the polymeric liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymeric liquid crystal composition.

[0251] [A laminate comprising a positive wavelength dispersive λ / 2 plate and a positive wavelength dispersive λ / 4 plate]

[0252] As one method to achieve anti-reflective properties, a laminate composed of a positive wavelength dispersive λ / 2 plate and a positive wavelength dispersive λ / 4 plate is known. For example, an illustrative laminate can be obtained by combining layers having the optical properties shown in Equations (QL1), (QL3), and (QL4) with layers having the optical properties shown in Equations (QL2), (QL3), and (QL4) in a specific slow-axis relationship.

[0253] 100nm<Re(550)<160nm (QL1)

[0254] 200nm<Re(550)<320nm (QL2)

[0255] Re(450) / Re(550)≥1.00(QL3)

[0256] 1.00≥Re(650) / Re(550)(QL4)

[0257] Examples of methods for combining the above-mentioned components include those disclosed in Japanese Patent Application Publication No. 2015-163935 and WO2013 / 137464. From the viewpoint of perspective compensation, it is preferable to use a λ / 2 layer of polymer containing a disc-shaped polymeric liquid crystal compound and a λ / 4 layer of polymer containing a rod-shaped polymeric liquid crystal compound.

[0258] Relative to the transmission axis of the linear polarizer, the slow axis of the positive wavelength dispersive λ / 2 layer is, for example, 10° to 20°, preferably 12° to 18°, and more preferably about 15°, and the slow axis of the positive wavelength dispersive λ / 4 layer is, for example, 70° or more and 80° or less, more preferably 72° or more and 78° or less, and more preferably about 75°.

[0259] In another embodiment, the slow axis of the positive wavelength dispersive λ / 2 layer is, for example, -10° to -20°, preferably -12° to -18°, more preferably about -15°, relative to the transmission axis of the linear polarizer, and the slow axis of the positive wavelength dispersive λ / 4 layer is, for example, -70° to -80°, more preferably -72° to -78°, more preferably about -75°.

[0260] In another embodiment, the slow axis of the positive wavelength dispersive λ / 2 layer is 70° to 80°, preferably 72° to 78°, and more preferably about 75°, relative to the transmission axis of the linear polarizer. The slow axis of the positive wavelength dispersive λ / 4 layer is, for example, 10° to 20°, more preferably 12° to 18°, and more preferably about 15°.

[0261] In another embodiment, the slow axis of the positive wavelength dispersive λ / 2 layer is -70° to -80°, preferably -72° to -78°, and more preferably about -75°, relative to the transmission axis of the linear polarizer. The slow axis of the positive wavelength dispersive λ / 4 layer is, for example, -10° to -20°, more preferably -12° to -18°, and more preferably about -15°.

[0262] Examples of disc-shaped polymeric liquid crystal compounds include compounds containing groups represented by formula (W) (hereinafter sometimes referred to as polymeric liquid crystal compounds (C)).

[0263] [Chemical Formula 7]

[0264]

[0265] In formula (W), R 40 Represent the following formulas (W-1) to (W-5).

[0266] [Chemical Formula 8]

[0267]

[0268] X 40 and Z 40 This refers to an alkyldiyl group with 1 to 12 carbon atoms, where the hydrogen atoms can be replaced by an alkoxy group with 1 to 5 carbon atoms, and the hydrogen atoms in the alkoxy group can be replaced by halogen atoms. Furthermore, the -CH2- group constituting this alkyldiyl group can be replaced by -O- or -CO-. Additionally, m2 is an integer from 1 to 20.

[0269] Examples of rod-shaped polymeric liquid crystal compounds include those represented by formulas (I), (II), (III), (IV), (V), or (VI).

[0270] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (I)

[0271] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (II)

[0272] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (III)

[0273] P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (IV)

[0274] P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (V)

[0275] P11-B11-E11-B12-A11-B13-A12-F11 (VI)

[0276] A11 represents a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. The hydrogen atoms contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be replaced by halogen atoms, alkyl groups with 1 to 6 carbon atoms, alkoxy groups with 1 to 6 carbon atoms, cyano groups or nitro groups, and the hydrogen atoms contained in the alkyl groups with 1 to 6 carbon atoms and the alkoxy groups with 1 to 6 carbon atoms may be replaced by fluorine atoms.

[0277] B11 represents -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 16 -, -NR 16 -CO-, -CO-, -CS-, or a single bond. R 16 It represents an alkyl group having 1 to 6 hydrogen atoms or carbon atoms.

[0278] B12 and B13 independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -O-C(=O)-, -O-C(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -, -NR 16 -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -O-C(=O)-CH=CH- or single bond.

[0279] E11 represents an alkyldiyl group with 1 to 12 carbon atoms. The hydrogen atoms in this alkyldiyl group can be replaced by alkoxy groups with 1 to 5 carbon atoms, and the hydrogen atoms in these alkoxy groups can be replaced by halogen atoms. Furthermore, the -CH2- group constituting this alkyldiyl group can be replaced by -O- or -CO-.

[0280] The number of carbon atoms in the aromatic hydrocarbon group and alicyclic hydrocarbon group of A11 is preferably in the range of 3 to 18, more preferably in the range of 5 to 12, and particularly preferably 5 or 6. As A11, cyclohexane-1,4-diyl or 1,4-phenylene are preferred.

[0281] As E11, a linear alkyldiyl group with 1 to 12 carbon atoms is preferred. The -CH2- group constituting this alkyldiyl group can be replaced by -O-.

[0282] Specifically, examples include straight-chain alkyl diyl groups with 1 to 12 carbon atoms, such as methylene, ethylene, propane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, nonane-1,9-diyl, decane-1,10-diyl, undecane-1,11-diyl, and dodecane-1,12-diyl; and -CH2-CH2-O-CH2-CH2-, -CH2-CH2-O-CH2-CH2-O-CH2-CH2-, and -CH2-CH2-O-CH2-CH2-O-CH2-CH2-.

[0283] As B11, -O-, -S-, -CO-O-, and -O-CO- are preferred, with -CO-O- being more preferred.

[0284] B12 and B13 are each preferably -O-, -S-, -C(=O)-, -C(=O)-O-, -O-C(=O)-, -O-C(=O)-O-, and more preferably -O- or -O-C(=O)-O-.

[0285] As the polymerizable group shown in P11, from the perspective of high polymerization reactivity, especially photopolymerization reactivity, free radical polymerizable groups or cationic polymerizable groups are preferred. From the perspective of ease of operation and ease of manufacturing the liquid crystal compound itself, the polymerizable group is preferably the group shown in the following formulas (P-11) to (P-15).

[0286] [Chemical Formula 9]

[0287]

[0288] In equations (P-11) to (P-15), R 17 ~R 21 Each can independently represent an alkyl group or a hydrogen atom having 1 to 6 carbon atoms.

[0289] As specific examples of the groups shown in formulas (P-11) to (P-15), the groups shown in formulas (P-16) to (P-20) can be cited below.

[0290]

Chemical Formula 10

[0291]

[0292] P11 is preferably a group represented by formula (P-14) to (P-20), more preferably vinyl, p-zirconia, epoxy or oxetyl.

[0293] The group shown in P11-B11- is further preferably acryloyloxy or methacryloyloxy.

[0294] (In the formula, A12 to A14 are each independently equivalent to A11, B14 to B16 are each independently equivalent to B12, B17 is equivalent to B11, and E12 is equivalent to E11. F11 represents a hydrogen atom, an alkyl group with 1 to 13 carbon atoms, an alkoxy group with 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfonyl group (-SO3H), a carboxyl group, an alkoxy carbonyl group with 1 to 10 carbon atoms, or a halogen atom. The -CH2- group constituting the alkyl and alkoxy groups can be replaced by -O-.)

[0295] [Other components]

[0296] In addition to the configuration of combining the above-mentioned positive wavelength dispersive λ / 2 layer and positive wavelength dispersive λ / 4 layer, the first and second liquid crystal phase retardation layers can also be a stack formed by tilting and cholesteric orientation of at least one liquid crystal phase retardation layer. Examples of known configurations include those disclosed in Publications WO2021 / 060378, WO2021 / 132616, and WO2021 / 132624.

[0297] <Positive C Board>

[0298] There are no particular limitations as long as the positive C plate is anisotropic in the thickness direction. Without tilting or cholesteric orientation, it has the optical properties shown in formula (PC3).

[0299] nx≈ny<nz (PC3)

[0300] The in-plane phase difference Re(550) at a wavelength of 550 nm for the positive C-plate is typically in the range of 0–10 nm, preferably in the range of 0–5 nm. Furthermore, the phase difference Rth(550) in the thickness direction at a wavelength of 550 nm is typically in the range of -170 nm to -10 nm, preferably -150 nm to -20 nm, and more preferably -100 nm to -40 nm. If the phase difference in the thickness direction is within this range, the anti-reflective properties in the tilt direction can be further improved.

[0301] The thickness of the positive C plate is typically less than 10 μm, preferably less than 5 μm, and more preferably more than 0.3 μm and less than 3 μm.

[0302] The positive C plate is preferably a coating layer formed by polymerizing one or more polymeric liquid crystal compounds. More preferably, it is a rod-shaped polymeric liquid crystal compound.

[0303] Examples of rod-shaped polymeric liquid crystals include compounds represented by formulas (I), (II), (III), (IV), (V), or (VI).

[0304] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (I)

[0305] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (II)

[0306] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (III)

[0307] P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (IV)

[0308] P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (V)

[0309] P11-B11-E11-B12-A11-B13-A12-F11 (VI)

[0310] (In the formula, A12 to A14 are each independently equivalent to A11, B14 to B16 are each independently equivalent to B12, B17 is equivalent to B11, and E12 is equivalent to E11. F11 represents a hydrogen atom, an alkyl group with 1 to 13 carbon atoms, an alkoxy group with 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfonyl group (-SO3H), a carboxyl group, an alkoxy carbonyl group with 1 to 10 carbon atoms, or a halogen atom. The -CH2- group constituting the alkyl and alkoxy groups can be replaced by -O-.)

[0311] Relative to 100 parts by mass of the solid component of the liquid crystal phase retardation layer formation composition, the content of the polymeric liquid crystal compound in the liquid crystal phase retardation layer formation composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass. If the content of the polymeric liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the obtained liquid crystal phase retardation layer. It should be noted that, in this specification, the solid component of the liquid crystal phase retardation layer formation composition refers to all components after removing volatile components such as organic solvents from the polymeric liquid crystal composition.

[0312] <Composition for forming liquid crystal phase retardation layer>

[0313] Liquid crystal phase retardation layers are typically formed by coating a liquid crystal phase retardation layer forming composition containing a polymerizable liquid crystal compound onto an alignment film to be formed as needed on a substrate, thereby polymerizing and curing the polymerizable liquid crystal compound in an aligned state.

[0314] [Orientation film and composition for forming orientation film]

[0315] The alignment film has an orientation constraint force that causes the polymerizable liquid crystal compound to align in a desired direction.

[0316] Alignment films facilitate the alignment of polymeric liquid crystal compounds. The states of liquid crystal alignment, such as horizontal alignment, vertical alignment, mixed alignment, and tilted alignment, vary depending on the properties of the alignment film and the polymeric liquid crystal compound, and their combinations can be arbitrarily chosen. For example, if the alignment film is a material exhibiting horizontal alignment as an alignment constraint force, the polymeric liquid crystal compound can form a horizontal or mixed alignment; if it is a material exhibiting vertical alignment, the polymeric liquid crystal compound can form a vertical or tilted alignment. The terms "horizontal," "vertical," etc., refer to the direction of the optical axis of the aligned polymeric liquid crystal compound relative to the plane of the optical anisotropy layer. For example, vertical alignment means that the optical axis of the aligned polymeric liquid crystal compound is in a direction perpendicular to the plane of the optical anisotropy layer. Here, "vertical" means 90° ± 20° relative to the plane of the optical anisotropy layer.

[0317] Regarding the orientation constraint force, when the orientation film is formed from an orientation polymer, it can be arbitrarily adjusted according to the surface condition and friction conditions; when it is formed from a photo-oriented polymer, it can be arbitrarily adjusted according to polarized light irradiation conditions, etc. Furthermore, liquid crystal orientation can also be controlled by selecting the surface tension, liquid crystal properties, and other physical properties of the polymerizable liquid crystal compound.

[0318] As an alignment film formed between a substrate and an optically anisotropic layer, an alignment film that is insoluble in the solvent used to form the optically anisotropic layer on the alignment film and has heat resistance in the heat treatment for solvent removal and liquid crystal alignment is preferred. Examples of alignment films include alignment films containing an alignment polymer, photoalignment films, groove alignment films, and stretch films stretched along the alignment direction. In the case of application to long, roll-shaped films, photoalignment films are preferred from the viewpoint that the alignment direction can be easily controlled.

[0319] The thickness of the alignment film is typically in the range of 10 nm to 5000 nm, preferably in the range of 10 nm to 1000 nm, and more preferably in the range of 30 nm to 300 nm.

[0320] Examples of orientation polymers used in friction-oriented films include polyamides and gelatin-like polymers with intramolecular amide bonds, polyimides and their hydrolysates (i.e., polyamic acid) with intramolecular imide bonds, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylates. Polyvinyl alcohol is preferred. These orientation polymers can be used alone or in combination of two or more.

[0321] One method for performing friction is to bring a film of an oriented polymer, formed on the surface of a substrate by coating an oriented polymer composition onto a substrate and annealing it, into contact with a friction roller wound with a friction cloth and rotating.

[0322] Photoalignment films contain polymers, oligomers, or monomers having photoreactive groups. The photoalignment film acquires orientation confinement force by irradiating polarized light. From the viewpoint that the direction of the orientation confinement force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light, photoalignment films are more preferred.

[0323] A photoreactive group is a group that generates liquid crystal alignment capability through light irradiation. Specifically, it is a group that undergoes a photoreaction, such as orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which is the origin of liquid crystal alignment capability. Among these photoreactive groups, groups that undergo dimerization or photocrosslinking reactions are preferred from the perspective of excellent alignment. As a photoreactive group capable of undergoing such reactions, a photoreactive group having unsaturated bonds, especially double bonds, is preferred, and a group having at least one selected from carbon-carbon double bonds (C=C bond), carbon-nitrogen double bonds (C=N bond), nitrogen-nitrogen double bonds (N=N bond), and carbon-oxygen double bonds (C=O bond) is more preferred.

[0324] Examples of photoreactive groups with C=C bonds include vinyl, polyenyl, linyl, linazolyl, linazoliumyl, chalcone, and cinnamoyl groups. Chalcone and cinnamoyl groups are preferred from the viewpoint of easy control of reactivity and the expression of orientation-restricting forces during photoorientation. Examples of photoreactive groups with C=N bonds include groups with structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups with N=N bonds include azophenyl, azonaphthyl, aromatic heterocyclic azo, diazo, and formazanyl groups, with azobenzene oxide as the basic structure. Examples of photoreactive groups with C=O bonds include benzophenone, coumarin, anthraquinone, and maleimide groups. These groups may have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and haloalkyl groups.

[0325] When irradiating with polarized light, the polarized light can be irradiated directly from the film surface or from the substrate side and transmitted through the polarized light. Furthermore, the polarized light is particularly preferably substantially parallel. Regarding the wavelength of the irradiated polarized light, it is preferable to use polarized light in the wavelength range where the photoreactive groups of the polymer or monomer containing photoreactive groups can absorb light energy. Specifically, UV (ultraviolet light) in the wavelength range of 250–400 nm is particularly preferred. Examples of light sources used for this polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF, and other ultraviolet lasers, with high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps being more preferred. These lamps are preferred because of the high luminous intensity of ultraviolet light at a wavelength of 313 nm. The light from the above-mentioned light source is irradiated by passing it through a suitable polarizer, thereby irradiating with polarized light. As the polarizer, polarizing filters, Glan-Thomson prisms, Glan-Taylor prisms, and wire-grid polarizers can be used.

[0326] The composition for forming the alignment film may contain a leveling agent as needed. As a leveling agent, silicone-based and / or fluorine-based leveling agents described in the section on liquid crystal phase difference layers (described later) may be used. The leveling agent is typically present in the solid components of the composition for forming the alignment film at a content preferably of 0.001 to 3% by mass, more preferably 0.01 to 3% by mass, and even more preferably 0.1 to 3% by mass.

[0327] (Composition for forming liquid crystal phase retardation layer)

[0328] Relative to 100 parts by mass of the solid component of the liquid crystal phase retardation layer formation composition, the content of the polymerizable liquid crystal compound in the liquid crystal phase retardation layer formation composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the obtained liquid crystal phase retardation layer. It should be noted that, in this specification, the solid component of the liquid crystal phase retardation layer formation composition refers to all components after removing volatile components such as organic solvents from the liquid crystal phase retardation layer formation composition.

[0329] In addition to the polymerizable liquid crystal compound mentioned above, the composition for forming a liquid crystal phase retardation layer may further include reactive additives such as solvents, leveling agents, polymerization initiators, photosensitizers, polymerization inhibitors, crosslinking agents, and binding agents.

[0330] <Solvent>

[0331] The composition for forming a liquid crystal phase retardation layer may contain a solvent. Generally, polymerizable liquid crystal compounds have high viscosity; therefore, by preparing a composition for forming a liquid crystal phase retardation layer that is dissolved in a solvent, coating becomes easier, resulting in easier formation of the liquid crystal phase retardation layer. As a solvent, a solvent capable of completely dissolving the polymerizable liquid crystal compound is preferred; furthermore, a solvent that is inactive in the polymerization reaction of the polymerizable liquid crystal compound is preferred.

[0332] Examples of solvents include: alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, and 1,3-dimethyl-2-imidazolinone. These solvents can be used alone or in combination of two or more.

[0333] The solvent content is preferably 50 to 98% by mass relative to the total amount of the liquid crystal phase retardation layer forming composition. In other words, the solid content in the liquid crystal phase retardation layer forming composition is preferably 2 to 50% by mass, more preferably 5 to 30% by mass. If the solid content is 50% by mass or less, the viscosity of the liquid crystal phase retardation layer forming composition becomes lower, and therefore the thickness of the liquid crystal phase retardation layer becomes approximately uniform, thus reducing the tendency for unevenness to occur in the liquid crystal phase retardation layer. Furthermore, the content of this solid content can be determined with consideration of the desired thickness of the optical anisotropy layer.

[0334] Leveling agent

[0335] The composition for forming a liquid crystal phase retardation layer may contain a leveling agent. A leveling agent is an additive that functions to adjust the flowability of the composition and make the film obtained by coating the composition flatter; examples include silicone-based leveling agents, acrylic-based leveling agents, and fluorinated leveling agents. Among these, silicone-based and fluorinated leveling agents, which have excellent functions in reducing the surface tension of the film obtained by coating the composition, are preferred.

[0336] Examples of silicone-based leveling agents include leveling agents with a polyorganosiloxane backbone.

[0337] Examples of groups that bond to silicon atoms (silicon atoms forming siloxane bonds) in polyorganosiloxanes include hydrocarbon groups. Organosilicon leveling agents can be leveling agents with two hydrocarbon groups bonded to silicon atoms.

[0338] There are no limitations on the groups that bond with silicon atoms, but alkyl or aryl groups with 1 to 10 carbon atoms are preferred, methyl or phenyl groups are more preferred, and methyl groups are even more preferred.

[0339] The groups that bond with silicon atoms can be only one type or more than two types.

[0340] In addition, the number of repeats (degree of polymerization) of the siloxane unit is not particularly limited, but is preferably 2 to 10,000, more preferably 3 to 5,000, and even more preferably 5 to 1,000.

[0341] Silicone-based leveling agents can be commercially available, such as SH710 (manufactured by Toray Dow Corning Co., Ltd.), BYK-300, BYK-302, BYK-306, BYK-307, BYK-310, BYK-313, BYK-315N, BYK-320, BYK-322, BYK-323, BYK-325, BYK-330, BYK-331, BYK-333, BYK-337, BYK-342, BYK-345, BYK-346, BYK-347, BYK-348, BYK-349, BYK-370, BYK-377, BYK-378, BYK-3455, BYK... BYK-Chemie Japan Co., Ltd., KF-945, KF-6015, KF-6020 (manufactured by Shin-Etsu Chemical Co., Ltd.), TEGORad2300, TEGORad2200N, and TEGORad2011 (manufactured by Degussa) are commercially available products containing free radical polymerizable groups such as (meth)acryloyl groups added to the polyether chain. Examples include BYK-UV3500, BYK-UV3505, BYK-3510, BYK-UV3530, BYK-UV3570, BYK-UV3575, and BYK-UV3576 (manufactured by BYK-Chemie Japan Co., Ltd.). (Made by Japan Co., Ltd.), KP-422, KP-416, KP-418, KP-410, KP-411, KP-412, KP-413, KP-423, KP-414, KP-415, KP-420, KP-983 (the above are manufactured by Shin-Etsu Chemical Co., Ltd.), etc.

[0342] Relative to 100 parts by mass of the polymerizable liquid crystal compound, the content of the organosilicon leveling agent in the liquid crystal phase difference layer forming composition is preferably 0.001 parts by mass to 2 parts by mass, more preferably 0.01 parts by mass to 1.5 parts by mass, and even more preferably 0.1 parts by mass to 1.5 parts by mass.

[0343] As a fluorinated leveling agent, there are no particular limitations; examples include leveling agents with a fluorinated aliphatic hydrocarbon skeleton.

[0344] The skeleton of the aforementioned fluoroaliphatic hydrocarbons is not particularly limited, and examples include fluoromethane, fluoroethane, fluoropropane, fluoroisopropane, fluorobutane, fluoroisobutane, fluorotert-butane, fluoropentane, fluorohexane, and other fluoroalkanes with 1 to 10 carbon atoms.

[0345] A fluorinated aliphatic hydrocarbon skeleton can be formed by replacing at least some of the hydrogen atoms with fluorine atoms, or it can be a perfluorinated aliphatic hydrocarbon skeleton in which all hydrogen atoms are replaced by fluorine atoms.

[0346] In addition, the aforementioned fluoroaliphatic hydrocarbon skeleton can form a polyfluoroalkylene ether skeleton as a repeating unit via ether bonds.

[0347] There are no particular limitations on the fluorinated aliphatic hydrocarbon group that serves as the repeating unit; examples include fluorinated C1-4 alkylene groups such as fluorinated methylene, fluorinated ethylene, fluorinated propylene, and fluorinated isopropylene.

[0348] The aforementioned fluorinated aliphatic hydrocarbon groups can be only one type or two or more types.

[0349] The number of repeats (degree of polymerization) of the fluoroalkylene ether unit is not particularly limited, but is preferably 10 to 10,000, more preferably 30 to 5,000, and even more preferably 50 to 1,000.

[0350] Examples of fluorinated leveling agents include commercially available products such as MEGAFACE (registered trademark) R-08, MEGAFACE R-30, MEGAFACE R-90, MEGAFACE F-410, MEGAFACE F-411, MEGAFACE F-443, MEGAFACE F-445, MEGAFACE F-470, MEGAFACE F-471, MEGAFACE F-477, MEGAFACE F-479, MEGAFACE F-482, MEGAFACE F-483, MEGAFACE F-281, MEGAFACE F-253, MEGAFACE F-251, MEGAFACE F-114, MEGAFACE F-510, MEGAFACE F-551, MEGAFACE F-552, MEGAFACE F-553, MEGAFACE F-554, etc. MEGAFACE MEGAFACE RS-75, MEGAFACE RS-76-E, MEGAFACE RS-76-NS, MEGAFACE RS-78, MEGAFACE RS-90, MEGAFACE DS-21 (DIC Corporation); Surflon (registered trademark) S-381, Surflon S-382, Surflon S-383, Surflon S-393, Surflon SC-101, Surflon SC-105, KH-40 and SA-100 (AGC SEIMI CHEMICAL Corporation); E1830, E5844 (Daikin Fine Chemicals Research Institute, Ltd.);EFTOP EF301, EFTOP EF303, EFTOP EF351 and EFTOP EF352 (Mitsubishi Materials Electronic Chemicals Co., Ltd.). ;

[0351] Relative to 100 parts by mass of the polymerizable liquid crystal compound, the content of the fluorine-based leveling agent in the liquid crystal phase difference layer forming composition is preferably 0.001 parts by mass to 2 parts by mass, more preferably 0.01 parts by mass to 1.5 parts by mass, and even more preferably 0.1 parts by mass to 1.5 parts by mass.

[0352] When the composition for forming a liquid crystal phase retardation layer contains various leveling agents, the amount is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. It should be noted that the composition for forming an optical anisotropic layer may contain two or more leveling agents.

[0353] <Polymerization Initiator>

[0354] The composition for forming a liquid crystal phase retardation layer may contain a polymerization initiator. A polymerization initiator is a compound capable of initiating a polymerization reaction of polymerizable liquid crystal compounds, etc. From the viewpoint of not depending on the phase state of the thermotropic liquid crystal, a photopolymerization initiator that generates active free radicals through the action of light is preferred as the polymerization initiator.

[0355] Any known photopolymerization initiator can be used, as long as it is a compound capable of initiating the polymerization reaction of a polymerizable liquid crystal compound. Specifically, photopolymerization initiators capable of generating active free radicals or acids through the action of light are examples, with photopolymerization initiators that generate free radicals through the action of light being preferred. Photopolymerization initiators can be used alone or in combination of two or more.

[0356] As photopolymerization initiators, known photopolymerization initiators can be used. For example, as photopolymerization initiators that generate active free radicals, self-cracking benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, azo compounds, etc., can be used. Hydrogen-abstracting compounds such as benzophenone compounds, alkylacetophenone compounds, benzoin ether compounds, benzoin ketal compounds, dibenzocycloheptenone compounds, anthraquinone compounds, xanthonesone compounds, thioxanthonesone compounds, haloacetophenone compounds, diekoxyacetophenone compounds, halodiimidazole compounds, halotriazine compounds, triazine compounds, etc., can be used. As photopolymerization initiators that generate acids, iodonium salts and sulfonium salts, etc., can be used. From the perspective of excellent reaction efficiency at low temperatures, self-destructive photopolymerization initiators are preferred, especially acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds.

[0357] The content of the polymerization initiator in the composition for forming the liquid crystal phase retardation layer can be appropriately adjusted according to the type and amount of the polymerizable liquid crystal compound. It is typically 0.1 to 30 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass. If the content of the polymerization initiator is within the above range, polymerization can be carried out without disturbing the orientation of the polymerizable liquid crystal compound.

[0358] <Sensitizer>

[0359] The composition for forming a liquid crystal phase retardation layer may contain a sensitizer. A photosensitizer is preferred as the sensitizer. Examples of such sensitizers include: xanthonesone compounds such as xanthonesone and thioxanthonesone (e.g., 2,4-diethylthioxanthonesone, 2-isopropylthioxanthonesone); anthracene compounds such as anthracene and alkoxy-containing anthracene (e.g., dibutoxyanthracene); phenothiazine and rubrene.

[0360] When the composition for forming the liquid crystal phase retardation layer contains a sensitizer, the polymerization reaction of the polymerizable liquid crystal compound contained in the composition can be further promoted. The amount of the sensitizer used is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass.

[0361] <Antioxidants>

[0362] From the viewpoint of stabilizing the polymerization reaction, compositions for forming liquid crystal phase retardation layers may contain antioxidants. Antioxidants allow for control over the extent of polymerization of the polymerizable liquid crystal compound.

[0363] The antioxidants mentioned above can be, for example, primary antioxidants selected from phenolic antioxidants, amine antioxidants, quinone antioxidants, and nitroso antioxidants, or secondary antioxidants selected from phosphorus antioxidants and sulfur antioxidants.

[0364] When the composition for forming the liquid crystal phase retardation layer contains an antioxidant, the antioxidant content is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. The antioxidant can be used alone or in combination of two or more types. If the antioxidant content is within the above range, polymerization can be carried out without disturbing the orientation of the polymerizable liquid crystal compound.

[0365] <Reactive Additives>

[0366] The composition for forming a liquid crystal phase retardation layer may include a reactive additive. Preferably, the reactive additive has a carbon-carbon unsaturated bond, an active hydrogen reactive group, or a thiol group within its molecule. It should be noted that the "active hydrogen reactive group" referred to here means a group reactive to groups with active hydrogen, such as carboxyl (-COOH), hydroxyl (-OH), and amino (-NH2). Glycidyl, oxazoline, carbodiimide, aziridinyl, imide, isocyanate, thioisocyanate, and maleic anhydride groups are representative examples. The number of reactive groups in the reactive additive is typically 1 to 20, preferably 1 to 10.

[0367] (Second adhesive layer 40)

[0368] The second adhesive layer 40 is disposed between the first liquid crystal phase reversal layer 30 and the second liquid crystal phase reversal layer 50, bonding them together. The second adhesive layer 40 can be in direct contact with the first liquid crystal phase reversal layer 30 and / or the second liquid crystal phase reversal layer 50. When at least one of the first liquid crystal phase reversal layer 30 and the second liquid crystal phase reversal layer 50 is formed on an alignment film, the second adhesive layer 40 can be in contact with that alignment film. The thickness of the second adhesive layer 40 is less than 100 nm. The thickness of the second adhesive layer can be less than 40 nm, or less than 30 nm, or less than 20 nm, or less than 15 nm, or less than 10 nm. The thickness of the second adhesive layer 40 can be 1 nm or more, or more than 2 nm, or more than 4 nm, or more than 6 nm.

[0369] The material of the second adhesive layer 40 is not particularly limited and can be a cationic polymeric adhesive or a free radical polymeric adhesive. However, from the viewpoint of satisfying the thickness of the second adhesive layer 40, a water-based adhesive layer is preferred.

[0370] The second adhesive layer 40, serving as the aqueous adhesive layer, can be formed by drying the aqueous adhesive composition. The aqueous adhesive composition is an adhesive composition formed from an aqueous solution of an adhesive resin dissolved in water. From the viewpoint of producing a thin adhesive, the concentration of the solid component in the aqueous adhesive composition is preferably 0.5% to 20% by mass, more preferably 1% to 15% by mass. The aqueous adhesive composition may contain crosslinking agents such as aldehyde compounds (glyoxal, etc.), epoxy compounds, melamine compounds, hydroxymethyl compounds, isocyanate compounds, amine compounds, and polyvalent metal salts.

[0371] Examples of resins used as the second adhesive layer 40 in water-based adhesives include urethane resins and polyvinyl alcohol (PVA) resins, with PVA resins being preferred.

[0372] When using a polyvinyl alcohol-based resin as the resin of the second adhesive layer 40, the polyvinyl alcohol-based resin can be partially saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, or a modified polyvinyl alcohol-based resin. Examples of modified polyvinyl alcohol-based resins include carboxyl-modified polyvinyl alcohol-based resins and acetyl-modified polyvinyl alcohol-based resins.

[0373] From the viewpoint of adhesion, the average degree of polymerization of polyvinyl alcohol-based resins (preferably acetyl-modified polyvinyl alcohol-based resins) is preferably 100 to 5500, more preferably 500 to 4500.

[0374] The degree of saponification of polyvinyl alcohol resins (preferably acetyl-modified polyvinyl alcohol resins) is typically 80 mol% to 100 mol%, preferably 85 mol% or more.

[0375] From the perspective of adhesion, the degree of modification (modification amount) of acetyl acetyl-based polyvinyl alcohol resin is usually 0.1 mol% to 40 mol%, preferably 0.5 mol% to 20 mol.

[0376] The resin of the second adhesive layer 40 is preferably a polyvinyl alcohol-based resin, and more preferably an acetyl-acetyl-modified polyvinyl alcohol-based resin. That is, the second adhesive layer 40 is preferably a dried and / or cured layer of an aqueous adhesive composition containing a polyvinyl alcohol-based resin.

[0377] To obtain a second adhesive layer of this thickness, for example, a liquid film can be formed by coating an adhesive solution, such as an aqueous adhesive solution, onto the surface of either the first liquid crystal phase reversal layer 30 or the second liquid crystal phase reversal layer 50. Then, the other of the first liquid crystal phase reversal layer 30 or the second liquid crystal phase reversal layer 50 is stacked on the liquid film. Finally, the solvent, such as water, in the liquid film is dried by heating or similar methods to form a thin second adhesive layer 40. After the drying process, ultraviolet light or an electron beam can be applied as needed.

[0378] At this point, by reducing the concentration of resin in the applied adhesive solution, even if a liquid film of, for example, about 2 μm is formed, a second adhesive layer with a thickness of less than 40 nm can be formed.

[0379] In addition, if the thickness of the first liquid crystal phase retardation layer 30 and the second liquid crystal phase retardation layer 50 is thin, the liquid film is prone to drying. Therefore, the thickness of both the first liquid crystal phase retardation layer 30 and the second liquid crystal phase retardation layer 50 is preferably 10 μm or less, preferably 5 μm or less, and more preferably 0.3 μm or more and 3 μm or less.

[0380] (In-plane average refractive index of the first and second liquid crystal phase refraction layers and the second adhesive layer)

[0381] The in-plane average refractive index of the first and second liquid crystal phase difference layers can be 1.45 to 1.65, preferably 1.50 to 1.60, and more preferably 1.53 to 1.58.

[0382] The in-plane average refractive index of the second adhesive layer can be 1.45 to 1.60, preferably 1.48 to 1.57, and more preferably 1.51 to 1.54.

[0383] (Outer adhesive layer 500)

[0384] The optical laminate 400 may have an outer adhesive layer 500 on the side opposite to the second adhesive layer 40 relative to the second liquid crystal phase difference layer 50.

[0385] The material and thickness of the outer adhesive layer 500 are not particularly limited. For example, various known adhesives such as acrylic adhesives, urethane adhesives, and silicone adhesives can be used. The thickness of the outer adhesive layer can be set to be 1 μm or more and 100 μm or less, and is preferably 5 μm or more and 50 μm or less.

[0386] (Mechanism of action)

[0387] According to this embodiment, an optical laminate can be provided that can simultaneously improve crack resistance under high temperature and high humidity environments and reduce unevenness when viewed through sunglasses. The reason for this is not yet clear, but it can be considered to be due to the following mechanism.

[0388] If the first adhesive layer 150 is a cured layer of a curable composition containing a cationic polymeric compound, compared with water-based adhesives and adhesive layers, the crosslinking density of the first adhesive layer 150 is higher. Therefore, even when exposed to high temperature and high humidity environments, it hinders the movement of deteriorating components (e.g., crosslinking components such as boron, acids containing iodine, etc.) from the linear polarizer to the second protective film. It is speculated that this is related to the improved durability of the second protective layer.

[0389] Furthermore, it is believed that since the thickness of the second adhesive layer 40 is less than 100 nm, the interference between the first liquid crystal phase difference layer 30 and the second liquid crystal phase difference layer 50 is in the ultraviolet region, which can suppress the interference unevenness under visible light from being observed, thereby suppressing the interference unevenness when viewed through sunglasses.

[0390] In addition, it is believed that if the curable resin composition of the first adhesive layer contains an oxobutane compound, it is easier to increase the crosslinking density and suppress cracks in high temperature and high humidity environments.

[0391] Furthermore, it is believed that if the curable resin composition of the first adhesive layer contains an alicyclic epoxy compound, it will also be effective in inhibiting deiodination under high temperature and high humidity conditions, especially when the polarizer contains iodine.

[0392] For example, when an online polarizer is a film that has been uniaxially stretched while impregnating dichroic pigments such as iodine and organic dichroic dyes into polymers such as polyvinyl alcohol resins, and the second protective layer is a triacetyl cellulose resin film, the following effects should be considered.

[0393] By humidifying the polarizer, the boric acid crosslinking in the polarizer is hydrolyzed, releasing iodine. The iodine then acts as an acid catalyst, causing the triacetyl cellulose resin membrane, which serves as the second protective layer, to hydrolyze.

[0394] It is believed that when the first protective layer is a triacetyl cellulose membrane, iodine diffuses outward from the polarizer through the first protective layer on the viewing side. However, when the first protective layer is a cyclic polyolefin resin membrane, iodine does not permeate through the first protective layer and thus remains inside the polarizer. Hydrolysis of the triacetyl cellulose membrane, which serves as the second protective layer, occurs significantly.

[0395] It is believed that by setting the first cured layer as a cured layer of a curable composition containing a cationic polymeric compound and delaying the permeation of iodine from the polarizer to the second protective layer, the hydrolysis of the second protective layer, which is a triacetylcellulose membrane, can be delayed, thereby suppressing cracking.

[0396] <Image display device>

[0397] An image display device comprises an optical laminate and an image display element (such as an organic EL display element). The optical laminate is disposed on the viewing side of the image display element (image display unit). An adhesive layer can be used to bond the optical laminate to the image display element.

[0398] Image display devices are not particularly limited, and examples include organic electroluminescent (organic EL) display devices, inorganic electroluminescent (inorganic EL) display devices, liquid crystal display devices, and electroluminescent display devices.

[0399] Image display devices can be used in mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic signage, measuring or measuring instruments, office equipment, medical equipment, electronic computing devices, etc.

[0400]

Example

[0401] The present invention will now be described in more detail with reference to embodiments and comparative examples, but the present invention is not limited to the following embodiments. Unless otherwise specified, “%” and “parts” in the examples refer to mass percentage and mass parts, respectively.

[0402] <Thickness Measurement>

[0403] The thickness of the layers was measured using a contact film thickness measuring device (Nikon MS-5C). The thickness of the aqueous adhesive layer was measured as follows: For the cross-section of the optically anisotropic laminate processed using an ultrathin slicer, the thickness was measured using a TEM (Hitachi High-Tech H-7650).

[0404] <Measurement of Phase Difference>

[0405] The phase difference values ​​of the first liquid crystal phase retardation film and the second liquid crystal phase retardation film were measured using a phase difference measuring device (KOBRA-WR, manufactured by Oji Keisha Machine Co., Ltd.). The phase difference value of the optical laminate containing the phase retardation layer was measured using a phase difference measuring device (KOBRA-PR, manufactured by Oji Keisha Machine Co., Ltd.) with the diaphragm 2 peeled off from the optical laminate and bonded to the glass. The in-plane phase difference values ​​for light with wavelengths of 450 nm, 550 nm, and 650 nm were obtained using the Cauchy dispersion formula derived from the measurement results of the in-plane phase difference values ​​for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm.

[0406] <Preparation of Water-Based Adhesives>

[0407] (Preparation of aqueous adhesive composition α)

[0408] At room temperature, the following components A-1 and B-1 were mixed at a mass ratio of 1:1 and stirred for 30 minutes to prepare an aqueous adhesive composition for forming an aqueous adhesive layer.

[0409] Composition A-1: ​​An aqueous solution of PVA with a solid content of 8% by mass was prepared by dissolving acetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with a 40% glyoxal aqueous solution to make the solid content mass ratio 3.0:0.7, and further adjusted to make the total solid content 3 parts per 100 parts of water, thus preparing composition A-1.

[0410] Composition Solution B-1: An aqueous PVA solution with a solid content of 8% by mass was prepared by dissolving acetoacetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with zinc chloride to make a mass ratio of 3.0:0.09, and further adjusted to make the total solid content 3 parts per 100 parts of water, thus preparing Composition Solution B-1.

[0411] (Preparation of aqueous adhesive composition β)

[0412] At room temperature, the following component liquid A-2 and component liquid B-2 are mixed at a mass ratio of 1:1 and stirred for 30 minutes to prepare an aqueous adhesive composition for forming an aqueous adhesive layer.

[0413] Composition A-2: An aqueous solution of PVA with a solid content of 8% by mass was prepared by dissolving acetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with a 40% glyoxal aqueous solution to make a mass ratio of 3.0:0.7, and further adjusted to make the total solid content 2 parts per 100 parts of water, thus preparing composition A-2.

[0414] Composition solution B-2: An aqueous solution of PVA with a solid content of 8% by mass was prepared by dissolving acetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with zinc chloride to make a mass ratio of 3.0:0.09, and further adjusted to make the total solid content 2 parts per 100 parts of water, thus preparing composition solution B-2.

[0415] (Preparation of aqueous adhesive composition γ)

[0416] At room temperature, the following components A-3 and B-3 are mixed at a mass ratio of 1:1 and stirred for 30 minutes to prepare an aqueous adhesive composition for forming an aqueous adhesive layer.

[0417] Composition A-3: An aqueous solution of PVA with a solid content of 8% by mass was prepared by dissolving acetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with a 40% glyoxal aqueous solution to make a mass ratio of 3.0:0.7, and further adjusted so that the total solid content relative to 100 parts of water was 1 part, thus preparing composition A-3.

[0418] Composition solution B-3: An aqueous solution of PVA with a solid content of 8% by mass was prepared by dissolving acetoacetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with zinc chloride to make a mass ratio of 3.0:0.09, and further adjusted so that the total solid content relative to 100 parts of water was 1 part, thus preparing composition solution B-3.

[0419] (Preparation of aqueous adhesive composition δ)

[0420] At room temperature, the following components A-4 and B-4 are mixed at a mass ratio of 1:1 and stirred for 30 minutes to prepare an aqueous adhesive composition for forming an aqueous adhesive layer.

[0421] Composition A-4: An aqueous solution of PVA with a solid content of 8% by mass was prepared by dissolving acetoacetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with a 40% glyoxal aqueous solution to make a mass ratio of 3.0:0.7, and further adjusted to make the total solid content 4 parts per 100 parts of water, thus preparing composition A-4.

[0422] Composition solution B-4: An aqueous solution of PVA with a solid content of 8% by mass was prepared by dissolving acetoacetyl-modified polyvinyl alcohol resin (manufactured by Mitsubishi Chemical Co., Ltd., "Gohsenol Z200") with a saponification degree of 99.2 mol% in water (distilled water). The prepared 8% by mass PVA solution was mixed with zinc chloride to make a mass ratio of 3.0:0.09, and further adjusted to make the total solid content 4 parts per 100 parts of water, thus preparing composition solution B-4.

[0423] <Preparation of Adhesive (1)>

[0424] After combining and mixing the following components, degassing is performed to prepare an active energy ray curable adhesive (1).

[0425] It should be noted that, in the following formulation amounts, the formulation amount of cationic polymerization initiator (CPI-100P) is the formulation amount of solid component.

[0426] [Catonic polymerizable compounds]

[0427] • 3',4'-Epoxycyclohexanecarboxylic acid methyl ester (Daicel, "CEL2021P"): 32.5 parts by weight

[0428]

Chemical Formula 11

[0429]

[0430] • Epoxy compounds containing alicyclic structures (Daicel "EHPE3150"): 7.5 parts by weight

[0431]

Chemical Formula 12

[0432]

[0433] ·3,3'-(oxybis(methylene)bis(3-ethyloxetane) (Toa Synthetic Co., Ltd. "OXT-221"): 60 parts by weight

[0434]

Chemical Formula 13

[0435]

[0436] [Photocationic polymerization initiator]

[0437] • Cationic polymerization initiator (trade name: CPI-100P_50% solution propylene carbonate solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by weight (actual solid content 2.25 parts by weight)

[0438] [Photosensitizing agent]

[0439] ·1,4-Diethoxynaphthalene: 2 parts by weight

[0440] <Preparation of Adhesive (2)>

[0441] After combining and mixing the following components, degassing is performed to prepare an active energy ray curing adhesive (2).

[0442] It should be noted that, in the following formulation amounts, the formulation amount of cationic polymerization initiator (CPI-100P) is the formulation amount of solid component.

[0443] [Catonic polymerizable compounds]

[0444] • 3',4'-Epoxycyclohexanecarboxylic acid methyl ester (Daicel, "CEL2021P"): 32.5 parts by weight

[0445] • Epoxy compound containing an alicyclic structure (Daicel "EHPE3150"): 27.5 parts by weight

[0446] ·3,3'-(oxybis(methylene)bis(3-ethyloxetane) (Toa Synthetic Co., Ltd., “OXT-221”): 40 parts by weight

[0447] [Photocationic polymerization initiator]

[0448] • Cationic polymerization initiator (trade name: CPI-100P_50% solution propylene carbonate solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by weight (actual solid content 2.25 parts by weight)

[0449] [Photosensitizing agent]

[0450] ·1,4-Diethoxynaphthalene: 2 parts by weight

[0451] <Preparation of adhesive (3)>:

[0452] After combining and mixing the following components, degassing is performed to prepare an active energy ray curing adhesive (3).

[0453] It should be noted that, in the following formulation amounts, the formulation amount of cationic polymerization initiator (CPI-100P) is the formulation amount of solid component.

[0454] [Catonic polymerizable compounds]

[0455] • 3',4'-Epoxycyclohexanecarboxylic acid methyl ester (Daicel, "CEL2021P"): 32.5 parts by weight

[0456] • Epoxy compound containing an alicyclic structure (Daicel "EHPE3150"): 47.5 parts by weight

[0457] ·3,3'-(oxybis(methylene)bis(3-ethyloxetane) (Toa Synthetic Co., Ltd., "OXT-221"): 20 parts by weight

[0458] [Photocationic polymerization initiator]

[0459] • Cationic polymerization initiator (trade name: CPI-100P_50% solution propylene carbonate solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by weight (actual solid content 2.25 parts by weight)

[0460] [Photosensitizing agent]

[0461] ·1,4-Diethoxynaphthalene: 2 parts by weight

[0462] <Preparation of Adhesive (4)>

[0463] The following components were combined and mixed, and then degassed to prepare an active energy ray curing adhesive (4).

[0464] [Catonic polymerizable compounds]

[0465] • 3,4-Epoxycyclohexanecarboxylic acid 3',4'-epoxycyclohexylmethyl ester (trade name: CEL2021P, manufactured by Daicel Co., Ltd.): 70 parts by weight

[0466] • Neopentyl glycol diglycidyl ether (trade name: EX-211, manufactured by Nagase ChemteX Co., Ltd.): 20 parts by weight

[0467] ·2-Ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Co., Ltd.): 10 parts by weight

[0468] [Photocationic polymerization initiator]

[0469] • Cationic polymerization initiator (trade name: CPI-100P_50% solution propylene carbonate solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by weight (actual solid content 2.25 parts by weight)

[0470] [Photosensitizing agent]

[0471] ·1,4-Diethoxynaphthalene: 2 parts by weight

[0472] <Preparation of Adhesive (5)>

[0473] After combining and mixing the following components, degassing is performed to prepare an active energy ray curing adhesive (5).

[0474] [Catonic polymerizable compounds]

[0475] • 3,4'-Epoxycyclohexanecarboxylic acid methyl ester (trade name: CEL2021P, manufactured by Daicel Co., Ltd.): 19 parts by weight

[0476] • Neopentyl glycol diglycidyl ether (trade name: EX-211, manufactured by Nagase ChemteX Co., Ltd.): 64 parts by weight

[0477] ·2-Ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Co., Ltd.): 7 parts by weight

[0478] • Poly GMA-MMA: 10 parts by weight

[0479] [Photocationic polymerization initiator]

[0480] • Cationic polymerization initiator (trade name: CPI-100P_50% solution propylene carbonate solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by weight (actual solid content 2.25 parts by weight)

[0481] <Preparation of Adhesive (6)>

[0482] After combining and mixing the following components, degassing is performed to prepare an active energy ray curable adhesive (6).

[0483] [Catonic polymerizable compounds]

[0484] Neopentyl glycol diglycidyl ether (trade name: EX-211L, manufactured by Nagase ChemteX Co., Ltd.) 30 parts by weight

[0485] ·3-Ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane (trade name: OXT-221, manufactured by Toa Synthetic Co., Ltd.) 13 parts by weight

[0486] • Bisphenol A type epoxy resin (trade name: EP-4100E, ADEKA Co., Ltd., viscosity 13 Pa·s (temperature 25°C)) 45 parts by weight

[0487] • Aromatic oxobutane compound (trade name: TCM-104, manufactured by TRONLY) 12 parts by weight

[0488] [Photocationic polymerization initiator]

[0489] • CPI-100P, manufactured by San-Apro Co., Ltd., 2.25 parts by weight of 50% propylene carbonate solution (solid content).

[0490] [Photosensitizing agent]

[0491] · 1 part by weight of 1,4-diethoxynaphthalene

[0492] <Preparation of Adhesive (7)>

[0493] After combining and mixing the following components, degassing is performed to prepare an active energy ray curable adhesive (7).

[0494] (Catonic polymeric compounds)

[0495] • 3,4'-Epoxycyclohexanecarboxylic acid methyl ester (trade name: CEL2021P, manufactured by Daicel Co., Ltd.): 32.5 parts

[0496] • 1,2-Epoxy-4-(2-Epoxyethylene)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (trade name: EHPE3150, manufactured by Daicel Co., Ltd.): 17.5 parts

[0497] ·3-[(benzyloxy)methyl]-3-ethyloxetane (an aromatic oxetane compound, trade name: TCM-104, manufactured by TRONLY): 10.0 parts

[0498] ·3-Ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane (trade name: OXT-221, manufactured by Toa Synthetic Co., Ltd.): 40.0 parts

[0499] (Photocationic polymerization initiator)

[0500] • Sulfonium photopolymerization initiator (trade name: CPI-100P, manufactured by San-Apro Co., Ltd., 50% by mass solution): 2.6 parts (actual solids content 1.3 parts)

[0501] (Photosensitizing agent)

[0502] ·1,4-Diethoxynaphthalene: 2.0 parts

[0503] <Preparation of Adhesive Layer (1)>

[0504] (1) Preparation of acrylic resin solution (1)

[0505] A mixed solution of 100 parts ethyl acetate, 99.0 parts butyl acrylate, 0.5 parts 2-hydroxyethyl acrylate, and 0.5 parts acrylic acid was added to a reaction vessel equipped with a condenser, a nitrogen inlet, a thermometer, and a stirrer. The internal temperature was raised to 55°C while purging the air in the apparatus with nitrogen to eliminate oxygen. Then, a solution containing 0.12 parts azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts ethyl acetate was added. After adding the polymerization initiator, the reaction vessel was kept at this temperature for 1 hour. Then, while maintaining the internal temperature at 54–56°C, ethyl acetate was continuously added to the reaction vessel at a rate of 17.3 parts / hr. The addition of ethyl acetate was stopped when the concentration of the (meth)acrylic resin reached 35% by mass. The reaction vessel was then kept at this temperature for another 6 hours from the start of the ethyl acetate addition. Finally, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass to prepare an acrylic resin solution (1). The obtained acrylic resin had a weight-average molecular weight (Mw) of 1.7 million and a molecular weight distribution (Mw / Mn) of 3.9. It should be noted that Mw and Mn were determined as follows: two TSKgel GMH resins manufactured by Tosoh Corporation were connected in series in the GPC apparatus. HR Using "-H(S)" as the column and tetrahydrofuran as the eluent, the determination was performed by conversion to standard polystyrene under the conditions of sample concentration of 2 mg / mL, sample introduction volume of 100 μL, temperature of 40℃, and flow rate of 1 mL / min.

[0506] (2) Preparation of adhesive composition (1)

[0507] Compared to the 80 parts of solid component of the acrylic resin solution (1) obtained above, 20 parts of difunctional acrylate (obtained from Shin-Nakamura Chemical Industry Co., Ltd.; product number "A-DOG") (solid component), 2.5 parts of crosslinking agent (manufactured by Tosoh Co., Ltd.: trade name "Coronate L" (ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate (solid component concentration 75% by mass)), 1.5 parts of photopolymerization initiator (manufactured by Ciba Specialty Chemicals Co., Ltd.: trade name "Irgacure 500"), and 0.3 parts of silane coupling agent (manufactured by Shin-Etsu Chemical Industry Co., Ltd.: trade name "KBM-403") were added, and ethyl acetate was further added to achieve a solid component concentration of 13% to obtain the adhesive composition (1).

[0508] A-DOG is a diacrylate of an acetal compound of hydroxypentanal and trimethylolpropane, having the following structure.

[0509]

Chemical Formula 14

[0510]

[0511] (3) Preparation of adhesive sheet (1)

[0512] Using an applicator, the adhesive composition (1) prepared above was applied to the release-treated surface of the membrane 1 ("PLZ-383030" obtained from Lintec Co., Ltd.) containing a polyethylene terephthalate film, which had undergone a release treatment, to a thickness of 5 μm after drying. The membrane was dried at 100°C for 1 minute to form an adhesive layer (1). Next, the surface of the adhesive layer (1) opposite to the membrane was bonded to the release-treated surface of the membrane 2 ("PLR-381031" obtained from Lintec Co., Ltd.), which had undergone a release treatment. Then, an adhesive sheet (1) comprising membrane 1 / adhesive layer (1) / membrane 2 was formed by irradiating with ultraviolet light under the following conditions. The refractive index of the adhesive sheet (1) for light with a wavelength of 589 nm was 1.48.

[0513] <UV Irradiation Conditions>

[0514] • Uses Fusion UV lamp system (manufactured by Fusion UV Systems) H bulb

[0515] • Cumulative light intensity 250 mJ / cm 2

[0516] <Preparation of Adhesive Layer (2)>

[0517] (1) Preparation of acrylic resin solution (2)

[0518] A mixed solution of 81.8 parts ethyl acetate, 90.0 parts butyl acrylate, 5.0 parts methyl acrylate, and 5.0 parts acrylic acid was added to a reaction vessel equipped with a condenser, a nitrogen inlet, a thermometer, and a stirrer. The internal temperature was raised to 55°C while purging the air in the apparatus with nitrogen to eliminate oxygen. Then, a solution containing 0.15 parts azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts ethyl acetate was added. After adding the polymerization initiator, the reaction vessel was kept at this temperature for 1 hour. Then, while maintaining the internal temperature at 54–56°C, ethyl acetate was continuously added to the reaction vessel at a rate of 17.3 parts / hr. The addition of ethyl acetate was stopped when the concentration of the (meth)acrylic resin reached 35% by mass. The reaction vessel was then kept at this temperature for another 6 hours from the start of the ethyl acetate addition. Finally, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass, thus preparing an acrylic resin solution (2). The obtained acrylic resin had a weight-average molecular weight (Mw) of 1.6 million and a molecular weight distribution (Mw / Mn) of 4.5. It should be noted that Mw and Mn were determined as follows: two TSKgel GMH resins manufactured by Tosoh Corporation were connected in series in a GPC apparatus. HR Using "-H(S)" as the column and tetrahydrofuran as the eluent, the determination was performed by conversion to standard polystyrene under the conditions of sample concentration of 2 mg / mL, sample introduction volume of 100 μL, temperature of 40℃, and flow rate of 1 mL / min.

[0519] (2) Preparation of adhesive composition (2)

[0520] Compared to 100 parts of the solid component of the acrylic resin solution (2) obtained above, 0.15 parts of crosslinking agent (manufactured by Tosoh Corporation; trade name "Coronate L" (ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate (solid component concentration 75% by mass)) and 0.2 parts of silane coupling agent (manufactured by Shin-Etsu Chemical Industry Co., Ltd.; trade name "KBM-403") were added based on the effective ingredient, and ethyl acetate was further added to make the solid component concentration 13%, thus obtaining the adhesive composition (2).

[0521] (3) Preparation of adhesive sheet (2)

[0522] Using an applicator, the adhesive composition (2) prepared above was applied to the release-treated surface of the separator 1 ("PLR-382190" obtained from Lintec Co., Ltd.) containing a polyethylene terephthalate film, with a dried thickness of 25 μm, and dried at 100°C for 1 minute to form an adhesive layer (2). Next, the surface of the adhesive layer (2) opposite to the separator was bonded to the release-treated surface of the separator 2 ("PET-251130" obtained from Lintec Co., Ltd.), containing a polyethylene terephthalate film, to form an adhesive sheet (2) comprising separator 1 / adhesive layer (2) / separator 2. The adhesive sheet (2) has a refractive index of 1.48 for light with a wavelength of 589 nm.

[0523] (Fabrication of linear polarizers)

[0524] A polyvinyl alcohol film with a thickness of 20 μm, a degree of polymerization of 2400, and a degree of saponification of 99% or higher is uniaxially stretched on a hot roller to a stretch ratio of 4.5 times. While maintaining tension, it is immersed for 60 seconds in a dyeing bath at 28°C containing 0.05 parts by mass of iodine and 5 parts by mass of potassium iodide relative to 100 parts by mass of water.

[0525] Next, the polarizer was immersed in an aqueous boric acid solution 1 at 64°C for 110 seconds, containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide relative to 100 parts by mass of water. Then, it was immersed in an aqueous boric acid solution 2 at 67°C for 30 seconds, containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide relative to 100 parts by mass of water. Finally, it was washed with pure water at 10°C and dried to obtain the polarizer. The polarizer had a thickness of 8 μm and a boron content of 4.3% by mass.

[0526] <Preparation of Polarizing Plate (1)>

[0527] The aqueous adhesive composition δ obtained above was coated on one side of the polarizer, and a COP film (cyclic olefin polymer film, manufactured by ZEON Corporation, Japan, 23 μm) was laminated to obtain a polarizing plate (1) with a protective film on one side of the polarizer. The layer structure of the polarizing plate is COP film / aqueous adhesive layer δ / polarizer.

[0528] <Preparation of Polarizing Plate (2)>

[0529] The aqueous adhesive composition δ obtained above was coated on one side of the polarizer, and a COP film (cyclic olefin polymer film, manufactured by ZEON Corporation, Japan, 23 μm) was laminated on it. The aqueous adhesive composition δ obtained above was coated on the other side of the polarizer, and a TAC film (triacetyl cellulose film, manufactured by Konica Minolta Corporation, 20 μm) was laminated on it. The film was dried at 80°C for 5 minutes, thereby obtaining a polarizing plate (2) with protective films on both sides of the polarizer. The layer structure of the polarizing plate is COP film / aqueous adhesive layer δ / polarizer / aqueous adhesive layer δ / TAC film.

[0530] <Fabrication of the First and Second Liquid Crystal Phase Retard Films>

[0531] (Preparation of the oriented polymer composition (1))

[0532] Water was added to commercially available polyvinyl alcohol (polyvinyl alcohol 1000 fully saponified type, manufactured by Wako Pure Chemical Industries Co., Ltd.), and the mixture was heated at 100°C for 1 hour to obtain an oriented polymer composition (1).

[0533] (Preparation of photooriented polymer composition (1))

[0534] The photo-oriented material with the following structure (weight average molecular weight: 50,000, m:n = 50:50) was manufactured according to the method described in Japanese Patent Application Publication No. 2021-196514. Two parts of the photo-oriented material and 98 parts of propylene glycol monomethyl ether (PGME, solvent) were mixed as components, and the resulting mixture was stirred at 80°C for 1 hour to prepare a photo-oriented polymer composition (1).

[0535] Photo-oriented materials:

[0536]

Chemical Formula 15

[0537]

[0538] (Manufacturing of polymeric liquid crystal compounds)

[0539] Polymerizable liquid crystal compounds (A1) and (A2) having the structures shown below were prepared respectively. The polymerizable liquid crystal compounds (A1) and (A2) were prepared in the same manner as described in Japanese Patent Application Publication No. 2010-244038.

[0540] Polymerizable liquid crystal compound (A1):

[0541] [Chemical Formula 16]

[0542]

[0543] Polymerizable liquid crystal compound (A2):

[0544]

Chemical Formula 17

[0545]

[0546] (Preparation of composition (Y1) for forming liquid crystal phase retardation film)

[0547] Polymerizable liquid crystal compound (A1) and polymerizable liquid crystal compound (A2) were mixed at a mass ratio of 80:20 to obtain a mixture. A leveling agent "Megaface F-556" (manufactured by DIC), a photopolymerization initiator "Omnirad 907" (manufactured by IGM Resin BV), and an ionic compound (B) were added relative to 100 parts of the obtained mixture. Furthermore, propylene glycol monomethyl ether acetate (PEGMEA) was added, and the mixture was stirred at 80°C for 1 hour to prepare a liquid crystal phase retardation film forming composition (Y1). The amounts of each component added are shown in Table 1 below.

[0548] Table 1

[0549]

[0550] Ionic compound (B):

[0551] [Chemical Formula 18]

[0552]

[0553] (Preparation of composition (Y2) for forming liquid crystal phase retardation film)

[0554] The polymerizable liquid crystal compound Paliocolor LC242 (manufactured by BASF Japan), the leveling agent "BYK-361N" (manufactured by BYK-Chemie), and "Omnirad907" (manufactured by IGM Resin BV) as a photopolymerization initiator were added. Furthermore, propylene glycol monomethyl ether acetate (PEGMEA) was added, and the mixture was stirred at 80°C for 1 hour to prepare a liquid crystal phase retardation film forming composition (Y2). The amounts of each component added are shown in Table 2 below.

[0555] Table 2

[0556]

[0557] Polymerizable liquid crystal compound LC242:

[0558] [Chemical Formula 19]

[0559]

[0560] <Fabrication of the film (Z1) with the first liquid crystal phase retardation film>

[0561] The permeability of a rectangular triacetyl cellulose (TAC) membrane (40 μm thick, 40 °C, 90% RH) is 950 g / m². 2 An oriented polymer composition (1) was coated onto a substrate for 24 hours to form an oriented polymer film with a thickness of 100 nm after heat drying. The surface of the obtained oriented polymer film was rubbed with the slow axis of the phase retardation film (Z1) formed below at an angle of -15° to the length direction of the aforementioned TAC. Based on this, a liquid crystal phase retardation film forming composition (Y1) was coated onto the substrate using a bar coater. The resulting coated film was dried at 100°C for 1 minute and then cooled to room temperature to obtain a dried film. Next, the dried film was irradiated with a nitrogen atmosphere using a high-pressure mercury lamp (USHIO Electric Co., Ltd. "Unicure VB-15201BY-A") with an exposure dose of 1000 mJ / cm. 2 Ultraviolet light (based on 365 nm) was used to solidify a first liquid crystal retardation film (X1) by curing a polymeric liquid crystal compound in a horizontally oriented state relative to the substrate plane. This resulted in a film (Z1) containing the TAC / orientation film / first liquid crystal retardation film (X1) (a horizontally oriented liquid crystal cured film). The thickness of the obtained first liquid crystal retardation film (X1) was measured using a laser microscope, and the result was 1.8 μm. The in-plane phase difference was measured using a KOBRA-WR instrument manufactured by Oji Measurement & Control Co., Ltd. The results showed that the in-plane phase difference at 550 nm was Re(550) = 270 nm, and the in-plane phase difference at 450 nm was Re(450) = 291 nm. It should be noted that the phase difference of the TAC at 550 nm is approximately 0, therefore it has no effect on the optical properties. The orientation angle relative to the length direction of the TAC was -15°.

[0562] <Fabrication of the film (Z2) with a second liquid crystal phase retardation film>

[0563] A triacetyl cellulose (TAC) membrane cut into rectangles (40 μm thickness, 40°C, 90% RH, with a permeability of 950 g / m³) 2A photo-aligned polymer composition (1) was coated onto a substrate (24hr). The resulting coated film was dried at 120°C for 2 minutes and then cooled to room temperature to form a dried film. Furthermore, 100 mJ of polarized ultraviolet light (313 nm reference) was continuously irradiated onto the substrate using a UV irradiation device at a 75° angle relative to the length direction of the TAC to form a 100 nm photo-aligned film. A liquid crystal phase retardation film forming composition (Y2) was then coated onto the substrate using a rod coater. The resulting coated film was dried at 100°C for 1 minute and then cooled to room temperature to obtain a dried film. Next, the dried film was continuously irradiated with an exposure dose of 1000 mJ / cm² under a nitrogen atmosphere using a high-pressure mercury lamp. 2 Ultraviolet light (based on 365 nm) was used to solidify a polymeric liquid crystal compound in a horizontally oriented state relative to the substrate plane to form a second liquid crystal retardation film (X2), resulting in a film (Z2) containing a TAC / orientation film / second liquid crystal retardation film (X2) (horizontally oriented liquid crystal cured film). The thickness of the obtained second liquid crystal retardation film (X2) was measured using a laser microscope, and the result was 1.0 μm. The in-plane phase difference value was measured using a KOBRA-WR manufactured by Oji Measurement & Control Co., Ltd. The results showed that the in-plane phase difference value at a wavelength of 550 nm was Re(550) = 142 nm, and the in-plane phase difference value at a wavelength of 450 nm was Re(450) = 153.4 nm. It should be noted that the phase difference value of the TAC at a wavelength of 550 nm is approximately 0, so it has no effect on the optical properties. The orientation angle relative to the length direction of the TAC is 75°.

[0564] <Fabrication of Phase Difference Stack (1)>

[0565] At 28kJ / m 2 Corona treatment was performed on the first liquid crystal phase retardation film (X1) with the first liquid crystal phase retardation film (Z1) and the second liquid crystal phase retardation film (X2) with the second liquid crystal phase retardation film (Z2). For the first liquid crystal phase retardation layer (X1) with the first liquid crystal phase retardation film (Z1) and the second liquid crystal phase retardation layer (X2) with the second liquid crystal phase retardation film (Z2), while supplying an aqueous adhesive composition α between them so that the thickness of the dried aqueous adhesive layer α is a specified thickness (8nm), the film (Z1) with the first liquid crystal phase retardation film and the film (Z2) with the second liquid crystal phase retardation film are aligned in the length direction, thereby bonding them together, and drying them in an atmospheric atmosphere at a temperature of 97°C for 12.3 minutes, thereby obtaining a phase retardation layer laminate (1) composed of TAC / alignment film / first liquid crystal phase retardation film (X1) / aqueous adhesive layer α / second liquid crystal phase retardation film (X2) / alignment film / TAC in sequence.

[0566] <Fabrication of Phase Difference Stack (2)>

[0567] Aqueous adhesive composition β was used instead of aqueous adhesive composition α, and the aqueous adhesive layer β was supplied in such a way that the thickness of the dried aqueous adhesive layer β was a specified thickness (5 nm). Otherwise, the same operation as the phase difference layer stack (1) was performed to obtain the phase difference layer stack (2).

[0568] <Fabrication of Phase Difference Stack (3)>

[0569] Aqueous adhesive composition γ was used instead of aqueous adhesive composition α, and the aqueous adhesive layer γ was supplied in such a way that the thickness of the dried aqueous adhesive layer γ was a specified thickness (3 nm). Otherwise, the same operation as the phase difference layer stack (1) was performed to obtain the phase difference layer stack (3).

[0570] <Fabrication of Phase Difference Stack (4)>

[0571] At 28kJ / m 2 Corona treatment was performed on the first liquid crystal phase retardation film (X1) with the first liquid crystal phase retardation film (Z1) and the second liquid crystal phase retardation film (X2) with the second liquid crystal phase retardation film (Z2). Adhesive (6) was coated on the first liquid crystal phase retardation film (X1) with the first liquid crystal phase retardation film (Z1) so that the thickness of the cured adhesive layer (6) was 2 μm. Then, the second liquid crystal phase retardation film (X2) with the second liquid crystal phase retardation film (Z2) was stacked on the adhesive coating (6). Ultraviolet light was irradiated from the side of the film (Z2) with the second liquid crystal phase retardation film to cure the adhesive (6) and form the adhesive layer (6). A phase retardation laminate (4) was obtained by sequentially stacking TAC / alignment film / first liquid crystal phase retardation film (X1) / adhesive layer (6) / second liquid crystal phase retardation film (X2) / alignment film / TAC. It should be noted that ultraviolet radiation, specifically UVA with wavelengths of 320nm–390nm, has a concentration of 420mJ / cm². 2 Irradiation is performed in this manner.

[0572] (Example 1)

[0573] A TAC membrane (triacetyl cellulose membrane, manufactured by Konica Minolta, 20 μm) was prepared. Adhesive (1) was coated on one side of the cured adhesive layer (1) to a thickness of 2 μm. The polarizing plate (1) of the polarizer (1) was then stacked on top of the adhesive coating. Ultraviolet light was irradiated from the TAC membrane side to cure the adhesive (1), thus forming the adhesive layer (1). This yielded an optical laminate A composed of COP membrane / water-based adhesive layer δ / polarizer / adhesive layer (1) / TAC membrane stacked sequentially. It should be noted that the ultraviolet light was UVA with a wavelength of 320 nm to 390 nm and a strength of 420 mJ / cm². 2 Irradiation is performed in this manner.

[0574] Peel diaphragm 1 from adhesive sheet (1) at 28 kJ / m 2 The adhesive layer (1) was corona treated under the following conditions. Then, the adhesive layer (1) was attached to the TAC film surface of the optical laminate A. The diaphragm 2 of the resulting laminate was peeled off and subjected to 28 kJ / m 2 Under the conditions of corona treatment, the other side of the adhesive layer (1) is subjected to corona treatment. After peeling off the TAC / alignment film on the first liquid crystal phase retardation layer (X1) side of the phase retardation stack (1), it is subjected to corona treatment at 28 kJ / m 2 The first liquid crystal phase retardation film (X1) is subjected to corona treatment under the following conditions. The first liquid crystal phase retardation film (X1) of the phase retardation layer stack is bonded to the adhesive layer (1) of the previously obtained optical stack A with adhesive layer (1) in such a way that the absorption axis of the polarizer is 90° with the length direction of the phase retardation layer stack (1), that is, the transmission axis of the polarizer is aligned with the length direction of the phase retardation layer stack. The alignment film / TAC on the second liquid crystal phase retardation film (X2) side of the obtained stack is peeled off, the separator 1 is peeled off from the adhesive sheet (2), and the adhesive layer (2) side is bonded to the second liquid crystal phase retardation film (X2). Thus, an optical stack is obtained by sequentially stacking COP film / water-based adhesive layer δ / polarizer / adhesive layer (1) / TAC film / adhesive layer (1) / first liquid crystal phase retardation film (X1) / water-based adhesive layer α / second liquid crystal phase retardation film (X2) / adhesive layer (2) / separator 2.

[0575] (Example 2)

[0576] The optical laminate is fabricated in the same manner as in Example 1, except that adhesive (2) is used instead of adhesive (1).

[0577] (Example 3)

[0578] The optical laminate is fabricated in the same manner as in Example 1, except that adhesive (3) is used instead of adhesive (1).

[0579] (Example 4)

[0580] The optical laminate is fabricated in the same manner as in Example 1, except that adhesive (4) is used instead of adhesive (1).

[0581] (Example 5)

[0582] The optical laminate is fabricated in the same manner as in Example 1, except that adhesive (5) is used instead of adhesive (1).

[0583] (Example 6)

[0584] The phase difference stack (2) is used instead of the phase difference stack (1), and the optical stack is otherwise fabricated in the same manner as in Example 1.

[0585] (Example 7)

[0586] The phase difference stack (3) is used instead of the phase difference stack (1), and the optical stack is otherwise made in the same manner as in Example 1.

[0587] (Example 8)

[0588] The optical laminate is fabricated in the same manner as in Example 1, except that adhesive (7) is used instead of adhesive (1).

[0589] (Example 9)

[0590] The adhesive (1) is applied so that the thickness of the adhesive layer (1) is 1.5 μm. Otherwise, the optical laminate is fabricated in the same manner as in Example 1.

[0591] (Comparative Example 1)

[0592] Peel diaphragm 1 from adhesive sheet (1) at 28 kJ / m 2 The adhesive layer (1) was corona treated under the following conditions. Then, the adhesive layer (1) was attached to the TAC film surface of the polarizing plate (2). The diaphragm 2 of the resulting laminate was peeled off and subjected to 28 kJ / m 2 Under certain conditions, the other side of the adhesive layer (1) was subjected to corona treatment to obtain an optical laminate B with adhesive layer (1) formed by sequentially stacking COP film / water-based adhesive layer δ / polarizer / water-based adhesive layer δ / TAC film / adhesive layer (1). After peeling off the TAC / alignment film on the first liquid crystal phase retardation film (X1) side of the phase retardation laminate (1), it was subjected to 28kJ / m 2Under certain conditions, the first liquid crystal phase retardation film (X1) is subjected to corona treatment. The first liquid crystal phase retardation film (X1) of the phase retardation layer stack is bonded to the adhesive layer (1) of the previously obtained optical stack B with adhesive layer (1) in such a way that the absorption axis of the polarizer is 90° with the length direction of the phase retardation layer stack (1), that is, the transmission axis of the polarizer is aligned with the length direction of the phase retardation layer stack. The alignment film / TAC on the second liquid crystal phase retardation film (X2) side of the obtained stack is peeled off, the separator 1 is peeled off from the adhesive sheet (2), and the adhesive layer (2) side is bonded to the second liquid crystal phase retardation film (X2). Thus, an optical stack is obtained by sequentially stacking COP film / water-based adhesive layer δ / polarizer / water-based adhesive layer δ / TAC film / adhesive layer (1) / first liquid crystal phase retardation film (X1) / water-based adhesive layer α / second liquid crystal phase retardation film (X2) / adhesive layer (2) / separator 2.

[0593] (Comparative Example 2)

[0594] Peel diaphragm 1 from adhesive sheet (1) at 28 kJ / m 2 Under certain conditions, the adhesive layer (1) was subjected to corona treatment. Then, the adhesive layer (1) was attached to the polarizer surface of the polarizer (1) to obtain an optical laminate C formed by sequentially stacking COP film / water-based adhesive layer δ / polarizer / adhesive layer (1) / membrane 2. Then, the optical laminate was fabricated in the same manner as in Example 1.

[0595] (Comparative Example 3)

[0596] The phase difference stack (4) is used instead of the phase difference stack (1), and otherwise it is made in the same way as Comparative Example 2.

[0597] <Evaluation>

[0598] (Durability evaluation of optical laminates: cracks)

[0599] Five pieces of the optical laminates obtained in Examples 1-7 and Comparative Examples 1-3 were cut into 80×80mm sizes. The diaphragm 2 was peeled off, and the optical laminates were bonded to the organic EL display element through the exposed adhesive layer (2) to fabricate an organic EL display device. The presence or absence of cracks was observed after the organic EL display device was stored at 85°C and 85%RH for 504 hours.

[0600] A: There were 5 samples that did not develop cracks.

[0601] B: The number of samples that did not develop cracks was 3.

[0602] D: The number of samples that did not develop cracks is 0.

[0603] (Durability evaluation of optical laminates: in-plane deiodination)

[0604] The in-plane deiodination behavior of the above-mentioned durable samples was observed.

[0605] A: Over 75% of the flour is free of iodine removal.

[0606] B: 50-75% of the flour is not deiodized.

[0607] C: More than 50% of the surface area undergoes deiodination.

[0608] (Thickness variation of the second protective layer (μm))

[0609] For organic EL display devices stored at 85°C and 85% humidity for 504 hours before and after a durability test, the thickness of the second protective layer in the central part of the optical laminate was measured using a Hitachi High-Tech VS1800 nano-optical interferometry system. The change in the thickness of the second protective layer was calculated by subtracting the thickness measurement before the durability test from the thickness measurement after the durability test. The average value of 5 samples was used. The thickness of the flat portion without cracks was measured. The thickness after the durability test was measured one day later. The decrease in film thickness was considered to be caused by hydrolysis, and the increase in thickness was considered to be caused by moisture absorption during the damp heat durability test.

[0610] (Evaluation of the inhomogeneity of optical laminates)

[0611] The optical laminates obtained in Examples 1-7 and Comparative Examples 1-3 were cut into 150mm × 150mm pieces. The cut optical laminates were attached to an aluminum reflector to obtain a test piece for observing interference inhomogeneities. With the ground angle set to 0°, the test piece for observing interference inhomogeneities was placed on a stage at an angle of 45° to the ground. Linear polarizers were positioned such that their transmission axes were orthogonal (orthogonal Nicol) between the three-wavelength fluorescent lamp (serving as a light source) and the test piece, and between the test piece and the observer. The three-wavelength fluorescent lamp light was shone onto the test piece from a 90° direction (above the test piece). When the observer viewed the test piece from the 0° direction, the test piece was rotated, and the test piece was observed and evaluated from various directions.

[0612] A: No uneven interference was observed.

[0613] B: Slight interference unevenness can be observed.

[0614] C: Observed uneven interference

[0615] D: Strong interference unevenness was observed.

[0616] (Determination of phase difference value of optical laminates including phase difference layer laminates)

[0617] The in-plane phase difference Re(λ) of the optical laminates containing the phase difference layer in Examples 1-9 and Comparative Examples 1-3 for light of wavelength λ was measured. The values ​​are as follows.

[0618] Re(450) = 106nm

[0619] Re(550) = 139nm

[0620] Re(450) / Re(550) = 0.76

[0621] Table 3 shows the composition of the cationic polymeric compounds in adhesive compositions (1) to (5) and (7). Additionally, Tables 4 and 5 show the conditions and results.

[0622] Table 3

[0623]

[0624] Table 4

[0625]

[0626] Table 5

[0627]

Claims

1. An optical laminate comprising, sequentially, a first protective layer, a linear polarizer, a first adhesive layer, a second protective layer, and a phase retardation layer. The first adhesive layer is a cured layer of a curable composition containing a cationic polymeric compound. The phase retardation layer stack comprises, from the first adhesive layer side, a first liquid crystal phase retardation layer, a second adhesive layer, and a second liquid crystal phase retardation layer in sequence. The thickness of the second adhesive layer is less than 100 nm.

2. The optical laminate according to claim 1, wherein, When all cationic polymeric compounds are set at 100 parts by weight, the curable composition of the first adhesive layer contains 20 to 80 parts by weight of an alicyclic epoxy compound.

3. The optical laminate according to claim 1 or 2, wherein, The cationic polymeric compound of the curable composition of the first adhesive layer contains an oxobutane compound.

4. The optical laminate according to claim 1 or 2, wherein, The second adhesive layer is a water-based adhesive layer.

5. The optical laminate according to claim 4, wherein, The thickness of the second adhesive layer is less than 20 nm.

6. The optical laminate according to claim 1 or 2, wherein, The second protective layer is a triacetyl cellulose resin film.

7. The optical laminate according to claim 1 or 2, wherein, When the in-plane phase difference of the phase difference layer stack with respect to light of wavelength λnm is set as Re(λ), the following relationships (1) and (2) are satisfied: 80nm≤Re(450)≤130nm (1) Re(450) / Re(550)≤1.00 (2).

Citation Information

Patent Citations

  • Optical film, retardation film, elliptical polarizing plate, liquid crystal display device and compound

    JP2010244038A

  • Optical film

    JP2015163935A

  • Polarizing plate composite and image display device

    JP2020052365A

  • Protective film for polarizing plate and polarizing plate using the same

    JP2021006929A

  • Polarizing film, polarizing plate, optical laminate, elliptical polarizing plate, organic el display, and flexible image display device

    JP2021196514A